Oxide solid electrolyte, binder, solid electrolyte layer, active material, electrode, all-solid-state secondary battery
By optimizing the composition of the oxide solid electrolyte and meeting specific physical characteristics, the problems of reduced contact area between particles and low heating treatment efficiency are solved, and better ion conductivity and battery safety are achieved.
Patent Information
- Application Number
- CN202180080416.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-09-22
- Filing Date
- 2021-12-01
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2041-12-01
AI Technical Summary
The oxide solid electrolyte has excellent safety and stability in the atmosphere, but its hardness leads to a decrease in the contact area between particles and increases the resistance of the interface. The existing heating treatment methods are inefficient and are not suitable for large-scale production.
By optimizing the composition of oxide solid electrolytes, it contains Li, B, O and specific element X, it meets specific X-ray total scattering and Raman spectral characteristics and improves its ion conductivity.
It achieves better ion conductivity of oxide solid electrolytes, reduces interface resistance, improves the safety and stability of the battery, and is suitable for large-scale production.
Smart Images

Figure CN116507587B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an oxide solid electrolyte, an adhesive, a solid electrolyte layer, an active material, an electrode and an all-solid-state secondary battery. Background Art
[0002] In the past, liquid electrolytes with high ion conductivity were used in lithium-ion secondary batteries. However, liquid electrolytes are flammable in most cases, which has safety issues. In addition, since they are liquid, they are difficult to miniaturize, and when batteries are enlarged, capacity restrictions also become a problem.
[0003] In contrast, all-solid-state secondary batteries are one of the next-generation batteries that can solve these problems. In order to obtain the desired charge and discharge characteristics in all-solid-state batteries, a solid electrolyte with good ion conductivity is required.
[0004] For example, Patent Document 1 describes an all-solid-state lithium-ion secondary battery comprising: a positive electrode layer comprising a positive electrode active material; a negative electrode layer comprising a negative electrode active material; and an oxide solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer, the oxide solid electrolyte layer comprising an oxide glass ceramic solid electrolyte containing Li3BO3 and Li2SO4, and the negative electrode active material in the negative electrode layer is coated with a hydride solid electrolyte so that the oxide glass ceramic solid electrolyte is not in direct contact with the negative electrode active material.
[0005] Previous technical literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2019-040709 Summary of the invention
[0008] Technical issues to be solved by the invention
[0009] Oxide solid electrolytes are excellent in terms of safety and stability in the atmosphere, but because their particles are relatively hard compared to soft and easily plastically deformed sulfide solid electrolytes, the contact area between particles becomes smaller, and there is a tendency for the resistance of the interface to increase. In order to improve the interparticle adhesion of oxide solid electrolytes and to improve ionic conductivity, it is known that there are techniques for heat treatments such as sintering and evaporation of oxide solid electrolytes. Regarding sintering, a high resistance phase sometimes occurs by the reaction of an active material with a solid electrolyte, and there is a problem of warping or cracking due to the shrinkage of the solid. The productivity of the evaporation method is low and is not suitable for mass production.
[0010] Therefore, the present inventors have conducted intensive studies on methods for improving ion conductivity of safe and excellent oxide solid electrolytes independently of the above-mentioned heat treatment, and have found that there is room for further improvement in the composition of the oxide solid electrolyte.
[0011] In view of the above-mentioned actual situation, an object of the present invention is to provide an oxide solid electrolyte having further excellent ion conductivity.
[0012] Furthermore, an object of the present invention is to provide a binder, a solid electrolyte layer, an active material, an electrode, and an all-solid-state secondary battery.
[0013] Means for solving technical problems
[0014] The present inventors have conducted intensive studies to solve the above-mentioned problems and have completed the present invention having the following configuration.
[0015] [1] An oxide solid electrolyte represented by the general formula (I) described below.
[0016] [2] The oxide solid electrolyte according to [1], which satisfies requirements 1-1 and 1-2 described below.
[0017] [3] An oxide solid electrolyte comprising Li, B, O and X and satisfying the requirements A-1 and A-2 described below.
[0018] X represents at least one element selected from F, Cl, Br, I, S, N, H, Se, Te, C, P, Si, Al, Ga, In, Ge, As, Sb and Sn.
[0019] [4] The oxide solid electrolyte according to any one of [1] to [3], wherein
[0020] Solid was heated at 120°C 7 The full width at half maximum of the peak whose chemical shift appears in the range of -100 to +100 ppm in the spectrum obtained by Li-NMR measurement is the same as that of the solid phase at 20°C. 7 In the spectrum obtained in the Li-NMR measurement, the ratio of the full width at half maximum of the peak in which the chemical shift appears in the range of -100 to +100 ppm is 70% or less.
[0021] [5] The oxide solid electrolyte according to any one of [1] to [4], wherein
[0022] In the Raman spectrum, the wavelength range is 600-850 cm -1 The coefficient of determination obtained by linear regression analysis based on the least squares method within the wavenumber region is above 0.9400.
[0023] [6] The oxide solid electrolyte according to any one of [1] to [5], wherein
[0024] The bulk modulus measured by an ultrasonic attenuation method is 45 GPa or less.
[0025] [7] The oxide solid electrolyte according to any one of [1] to [6], wherein
[0026] The X includes at least one selected from F, Cl, Br, I, Se, Te and H and at least one selected from C, P, S and N.
[0027] [8] An adhesive represented by the general formula (I) described below.
[0028] [9] The adhesive according to [8], which satisfies the requirements 1-1 and 1-2 described below.
[0029]
[10] A binder comprising Li, B, O and X and satisfying the requirements A-1 and A-2 described below.
[0030] X represents at least one element selected from F, Cl, Br, I, S, N, H, Se, Te, C, P, Si, Al, Ga, In, Ge, As, Sb and Sn.
[0031]
[11] The adhesive according to any one of [8] to
[10] , wherein
[0032] Solid was heated at 120°C 7 The full width at half maximum of the peak whose chemical shift appears in the range of -100 to +100 ppm in the spectrum obtained by Li-NMR measurement is the same as that of the solid phase at 20°C. 7 In the spectrum obtained in the Li-NMR measurement, the ratio of the full width at half maximum of the peak in which the chemical shift appears in the range of -100 to +100 ppm is 70% or less.
[0033]
[12] The adhesive according to any one of [8] to
[11] , wherein
[0034] In the Raman spectrum, the wavelength range is 600-850 cm -1 The coefficient of determination obtained by linear regression analysis based on the least squares method within the wavenumber region is above 0.9400.
[0035]
[13] The adhesive according to any one of [8] to
[12] , wherein
[0036] The bulk modulus measured by an ultrasonic attenuation method is 45 GPa or less.
[0037]
[14] The adhesive according to any one of [8] to
[13] , wherein
[0038] The X includes at least one selected from F, Cl, Br, I, Se, Te and H and at least one selected from C, P, S and N.
[0039]
[15] A solid electrolyte layer located between a positive electrode and a negative electrode and comprising the oxide solid electrolyte described in any one of [1] to [7].
[0040]
[16] An active material for an all-solid-state secondary battery, wherein:
[0041] At least a portion of the surface of the active material is coated with a coating layer comprising the oxide solid electrolyte described in any one of [1] to [7].
[0042]
[17] An electrode for an all-solid-state secondary battery, comprising:
[0043] An active material layer comprising an active material and at least one of the oxide solid electrolytes described in any one of [1] to [7] and the binder described in any one of [8] to
[14] ; and a current collector.
[0044]
[18] An electrode for an all-solid-state secondary battery, comprising an active material layer containing the active material for an all-solid-state secondary battery according to
[16] and a current collector.
[0045]
[19] An all-solid-state secondary battery comprising a positive electrode, a negative electrode and a solid electrolyte layer located between the positive electrode and the negative electrode, wherein at least one of the positive electrode, the negative electrode and the solid electrolyte layer comprises an oxide solid electrolyte selected from any one of [1] to [7] and at least one of the binders selected from any one of [8] to
[14] .
[0046]
[20] The all-solid-state secondary battery according to
[19] , wherein:
[0047] The above-mentioned solid electrolyte layer is the solid electrolyte layer described in
[15] .
[0048]
[21] The all-solid-state secondary battery according to
[19] or
[20] , wherein:
[0049] At least one of the positive electrode and the negative electrode is the electrode for an all-solid-state secondary battery according to
[17] or
[18] .
[0050] Effects of the Invention
[0051] According to the present invention, it is possible to provide an oxide solid electrolyte having further excellent ion conductivity.
[0052] Furthermore, according to the present invention, a binder, a solid electrolyte layer, an active material, an electrode, and an all-solid-state secondary battery can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 This is a diagram showing an example of a reduced pair distribution function G(r) obtained by total X-ray scattering measurement of the oxide solid electrolyte of the present invention.
[0054] Figure 2 This is a diagram showing an example of the total X-ray scattering profile of the oxide solid electrolyte of the present invention.
[0055] Figure 3 Is based on Figure 2 A diagram showing an example of the structure factor S(Q) of the total X-ray scattering profile obtained in .
[0056] Figure 4 The solid state of the oxide solid electrolyte of the present invention is obtained by heating the solid state of the oxide solid electrolyte of the present invention at 20°C or 120°C. 7 A diagram showing an example of a spectrum obtained during Li-NMR measurement.
[0057] Figure 5 It means that the solid of lithium tetraborate crystals is carried out at 20℃ or 120℃ 7 A diagram showing an example of a spectrum obtained during Li-NMR measurement.
[0058] Figure 6 This is a diagram showing an example of the Raman spectrum of the oxide solid electrolyte of the present invention.
[0059] Figure 7 This is a diagram showing a Raman spectrum of a general lithium tetraborate crystal.
[0060] Figure 8 It is a cross-sectional view showing an example of the structure of the all-solid-state secondary battery of the present invention.
[0061] Fig. 9 Graph showing the reduced two-body distribution function G(r) obtained by total X-ray scattering measurement of the LBO powder of Comparative Example 1.
[0062] Fig.10 This is a diagram showing an example of an X-ray diffraction pattern for explaining requirement 3.
[0063] Fig.11 This is a diagram showing the X-ray diffraction pattern of the LBO powder of Comparative Example 1.
[0064] Fig.12 This is a diagram showing the X-ray diffraction pattern of the oxide solid electrolyte of Example 2. DETAILED DESCRIPTION
[0065] Hereinafter, the present invention will be described in detail.
[0066] In the present specification, a numerical range expressed using "to" means a range including the numerical values described before and after "to" as the lower limit and the upper limit.
[0067] In this specification, the label of a compound (for example, when ending with "compound") includes the meaning of its salt and its ion in addition to the compound itself. Furthermore, the label of a compound includes the meaning of a derivative obtained by changing a part such as introducing a substituent, within the scope that does not impair the effects of the present invention.
[0068] [Oxide Solid Electrolyte (First Embodiment)]
[0069] As a first embodiment of the present invention, the following oxide solid electrolytes can be mentioned.
[0070] The oxide solid electrolyte of the present embodiment is represented by the following general formula (I).
[0071] A a B b O c X d (I)
[0072] In the general formula (I), A represents at least one selected from Li and Na.
[0073] X represents at least one selected from F, Cl, Br, I, S, N, H, Se, Te, C, P, Si, Al, Ga, In, Ge, As, Sb and Sn.
[0074] a represents the number of moles of each element represented by A, and is 1.75<a<2.45.
[0075] b is 3.75<b<4.25.
[0076] c is 6.50<c<10.00.
[0077] d represents the total number of moles of the element represented by X, and is 0<d<0.50.
[0078] The oxide solid electrolyte of the present embodiment contains an element represented by A (hereinafter also referred to as “element A”), B, and O, and further contains an element represented by X (hereinafter also referred to as “element X”).
[0079] The present inventors have found that the oxide solid electrolyte exhibits an excellent effect of improving ion conductivity by containing predetermined amounts of the elements A, B, and O, respectively, and also containing a predetermined amount of the element X.
[0080] Hereinafter, the oxide solid electrolyte represented by the general formula (I) of the present embodiment is also described as a “first specific solid electrolyte”.
[0081] Next, the elemental composition of the first specific solid electrolyte will be described.
[0082] The element A is at least one selected from Li (lithium element) and Na (sodium element). Among them, from the viewpoint of better ion conductivity (hereinafter also referred to as "the viewpoint of better effect of the present invention"), the element A is preferably Li.
[0083] From the viewpoint of further improving the effect of the present invention, a is preferably 1.75<a<2.25, and more preferably 1.90<a<2.10.
[0084] b represents the number of moles of B (boron element). b is preferably 3.90<b<4.10, and more preferably b=4.00.
[0085] c represents the number of moles of O (oxygen element). c is preferably 6.50<c<10.00, more preferably 7.00<c<9.80.
[0086] The element X is at least one selected from the group consisting of F (fluorine), Cl (chlorine), Br (bromine), I (iodine), S (sulfur), N (nitrogen), H (hydrogen), Se (selenium), Te (tellurium), C (carbon), P (phosphorus), Si (silicon), Al (aluminum), Ga (gallium), In (indium), Ge (germanium), As (arsenic), Sb (antimony) and Sn (tin).
[0087] The first specific solid electrolyte may contain only one element X, or may contain two or more elements X.
[0088] d represents the total number of moles of element X. d is preferably 0<d<0.40, more preferably 0<d<0.20.
[0089] The first specific solid electrolyte preferably contains at least F, Cl, Br, I, S, N, Se, or Te as the element X.
[0090] When the first specific solid electrolyte contains only one element X, the element is preferably X, F, Cl, or I, more preferably Cl or I, and further preferably I.
[0091] When the first specific solid electrolyte contains two or more elements X, the element X preferably contains at least one selected from F, Cl, Br, I, Se, Te and H and at least one selected from C, P, S and N, and more preferably contains at least one selected from F, Cl and I and at least one selected from S and N.
[0092] Among them, when the first specific solid electrolyte contains two or more elements X, the element X is more preferably an embodiment containing F and at least one selected from S and N, and the element X is particularly preferably an embodiment containing F, S, and N.
[0093] The type and content of each element contained in the first specific solid electrolyte can be determined by performing a known elemental analysis. The elemental analysis of the first specific solid electrolyte can be performed in different ways according to the characteristics of each element. For example, as a method of elemental analysis, Li, Na and B are analyzed by ICP-OES (Inductively coupled plasma optical emission spectrometry), in X, N is analyzed by inert gas fusion method, F, Cl, Br, I and S are analyzed by combustion ion chromatography (combustion IC: Ion Chromatography), and Se and Te are analyzed by ICP-OES. For O, the analyzed masses of elements other than O are added and calculated as a difference from the total amount of powder.
[0094] The first specific solid electrolyte may be a compound formed by doping a compound composed of Li, B, and O with at least one element X. Examples of the compound composed of Li, B, and O include lithium tetraborate compounds described below. The element doped into the first specific solid electrolyte is not particularly limited as long as it is an element described as the element X, but the element X cited as the preferred embodiment is preferred.
[0095] The method for producing the doped compound is not particularly limited, and an example thereof includes a method comprising subjecting a lithium tetraborate compound to mechanical milling in the presence of a specific element source described below.
[0096] In addition, in this specification, the symbol "solid electrolyte" means a solid compound having a function of moving ions inside. The shape and size of the solid electrolyte (including the first specific solid electrolyte and the second specific solid electrolyte described later) are not limited as long as it has the above-mentioned function.
[0097] In the following description of each embodiment of the present invention, lithium ions are sometimes cited as an example for explanation as charge carriers that are responsible for giving, accepting, and moving charges. However, the charge carriers are not limited to lithium ions, and may be sodium ions, magnesium ions, aluminum ions, potassium ions, hydrogen ions, oxygen ions, or fluoride ions.
[0098] (physical properties)
[0099] <Requirements 1-1 and 1-2>
[0100] The first specific solid electrolyte preferably satisfies the following requirements 1-1 and 1-2.
[0101] Requirement 1-1: In the reduced two-body distribution function G(r) obtained from the X-ray total scattering measurement of the first specific solid electrolyte, there is a peak located at r. The first peak and the top peak in the range of r are The second peak in the range of , the G(r) of the top of the first peak and the G(r) of the top of the second peak are greater than 1.0.
[0102] Requirement 1-2: In the reduced two-body distribution function G(r) obtained from the X-ray total scattering measurement of the first specific solid electrolyte, when r is greater than And for In the following range, the absolute value of G(r) is less than 1.0.
[0103] In the following, regarding requirements 1-1 and 1-2, Figure 1 Provide explanation.
[0104] exist Figure 1 An example of the reduced two-body distribution function G(r) obtained by total X-ray scattering measurement of the first specific solid electrolyte is shown in FIG. Figure 1 The vertical axis is the reduced two-body distribution function obtained by Fourier transforming X-ray scattering, and represents the probability of the existence of an atom at a distance r.
[0105] In SPring-8BL04B2 (acceleration voltage 61.4keV, wavelength ) was used for total X-ray scattering measurement.
[0106] In addition, the scattering intensity I obtained by the experiment was transformed in the following procedure to obtain the reduced two-body distribution function G(r).
[0107] First, the scattering intensity I obs It is represented by formula (1). And the structure factor S(Q) is obtained by dividing I coh It is obtained by dividing the product of the number of atoms N and the atomic scattering factor f.
[0108] I obs =I coh +I incoh +I 荧光 (1)
[0109] [Formula 1]
[0110]
[0111] PDF (Pair Distribution Function) analysis requires the use of the structure factor S(Q). In the above equation (2), the required intensity is only the coherent scattering I coh . Incoherent scattering I incoh and Fluorescent X-ray I 荧光 can be used to measure the blank, subtract the theoretical formula and pass the detector's discriminator from the scattered intensity I obs An example of the total scattering measurement results of the first specific solid electrolyte and the extracted structure factor S(Q) is shown in Figure 2 and Figure 3 middle.
[0112] Coherent scattering is expressed by Debye's scattering equation (3) (N: total number of atoms, f: atomic scattering factor, r ij : the interatomic distance between ij).
[0113] [Formula 2]
[0114]
[0115] If we focus on an arbitrary atom and let the atomic density at a distance r be ρ(r), then the number of atoms existing in a sphere with a radius of r-r+d(r) is 4πr. 2 ρ(r)dr, so equation (3) is expressed by equation (4).
[0116] [Formula 3]
[0117]
[0118] If the average density of atoms is set to ρ0 and equation (4) is transformed, equation (5) can be obtained.
[0119] [Formula 4]
[0120]
[0121] By using equation (5) and equation (2), we can obtain equation (6).
[0122] [Formula 5]
[0123]
[0124] The two-body distribution function g(r) is expressed by equation (7).
[0125] [Formula 6]
[0126]
[0127] By using the above equations (6) and (7), equation (8) can be obtained.
[0128] [Formula 7]
[0129]
[0130] As mentioned above, the two-body distribution function can be obtained by Fourier transforming the structure factor S(Q). In order to easily observe the order at medium / long distances, the two-body distribution function is transformed into G(r)=4πr(g(r)-1), that is, the restored two-body distribution function ( Figure 1 ). g(r) oscillating around 0 represents the density difference from the average density at each interatomic distance, and when there is a correlation at a specific interatomic distance, the average density is higher than 1. Therefore, the distance and coordination number of the element corresponding to the local to the medium distance are reflected. If the order is lost, ρ(r) approaches the average density, so g(r) gradually approaches 1. Therefore, in an amorphous structure, the larger r becomes, the more order is lost, so g(r) becomes 1, that is, G(r) becomes 0.
[0131] If requirement 1-1 is met, Figure 1 As shown, in the reduced two-body distribution function G(r) obtained from the X-ray total scattering measurement, there is a peak located at r The first peak P1 and the top peak within the range of r are The second peak P2 within the range of , the G(r) of the top of the first peak P1 and the G(r) of the top of the second peak P2 are greater than 1.0.
[0132] That is, in the reduced two-body distribution function G(r) obtained from the X-ray total scattering measurement of the first specific solid electrolyte, G(r) where a peak (hereinafter also referred to as "the first peak") is observed is greater than 1.0, and the first peak is located at The G(r) of the first peak and the top peak (hereinafter also referred to as the "second peak") in the range of The second peak in the range.
[0133] In addition, Figure 1 The peak of the first peak P1 is located at The peak of the second peak P2 is located at
[0134] exist There is a peak at the position of B (boron)-O (oxygen) interatomic distance. That is, the observation of the above two peaks (the first peak and the second peak) means that a periodic structure corresponding to the above two interatomic distances exists in the first specific solid electrolyte.
[0135] Furthermore, if requirements 1-2 are met, Figure 1 As shown, when r is greater than And for In the following range, the absolute value of G(r) is less than 1.0 (corresponding to the area sandwiched by the two dotted lines).
[0136] As mentioned above, when r is greater than And for In the following range, the absolute value of G(r) being less than 1.0 means that there is almost no long-range ordered structure in the first specific solid electrolyte.
[0137] As described above, the first specific solid electrolyte that satisfies the above-mentioned requirements 1-1 and 1-2 has a short-range order structure related to the interatomic distance of B-0 and BB, but has almost no long-range order structure. Therefore, the first specific solid electrolyte itself shows elastic properties that are softer and easier to plastically deform than previous lithium-containing oxides. As a result, it is speculated that in the molded body of the first specific solid electrolyte formed by pressure treatment, the adhesion between the first specific solid electrolytes and / or the adhesion between the first specific solid electrolyte and other ion conductors is improved, and the interface resistance can be reduced, and more excellent ion conductivity can be obtained.
[0138] In addition, in the above-mentioned reduced two-body distribution function G(r), when r is In the following ranges, peaks other than the first peak and the second peak may exist.
[0139] <Solid 7 Li-NMR spectral characteristics>
[0140] From the viewpoint of further improving the effect of the present invention, the first specific solid electrolyte is subjected to solidification at 20° C. and 120° C. 7 In the Li-NMR measurement, the full width at half maximum ratio calculated by the following method from the spectrum obtained is preferably 70% or less, more preferably 50% or less. The lower limit is not particularly limited, but is often 10% or more.
[0141] The full width at half maximum ratio is obtained by performing solidification of the first specific solid electrolyte at 20°C and 120°C. 7In Li-NMR measurement, the half-maximum full width (half-maximum full width 1) of the peak in the range of -100 to +100 ppm in the spectrum obtained by the measurement at 20°C and the half-maximum full width (half-maximum full width 2) of the peak in the range of -100 to +100 ppm in the spectrum obtained by the measurement at 120°C are calculated, and then the percentage of the ratio of the half-maximum full width 2 to the half-maximum full width 1 is calculated {(half-maximum full width 2 / half-maximum full width 1) × 100} is obtained.
[0142] The full width at half maximum (FWHM) of a peak refers to the width (ppm) at a point (H / 2) that is half the height (H) of the peak.
[0143] Below, use Figure 4 The above characteristics are described.
[0144] exist Figure 4 The solid of the first specific solid electrolyte is shown in 7 An example of a spectrum obtained during Li-NMR measurement.
[0145] Figure 4 The solid line spectrum shown on the lower side is a spectrum of solid 7 The spectrum obtained during Li-NMR measurement is Figure 4 The dotted spectrum shown on the upper side is a spectrum of solid 7 Spectrum obtained during Li-NMR measurement.
[0146] In general, in solid 7 In the Li-NMR measurement, Li + In case of high mobility, the peaks obtained are sharper. Figure 4 In the method shown in , when comparing the spectrum at 20°C and the spectrum at 120°C, the spectrum at 120°C becomes sharper. Figure 4 In the embodiment shown in FIG. 1 , it is shown that due to the presence of Li defects, Li + The mobility of the first specific solid electrolyte is increased. It is believed that the first specific solid electrolyte becomes easy to plastically deform due to the defect structure as described above, and the Li + The jumping property of the present invention is excellent and the effect of the present invention is even better.
[0147] In addition, regarding general lithium tetraborate crystals, solid 7 When Li-NMR is measured, it is shown in Figure 5 The spectrum measured at 20°C indicated by the solid line on the lower side is consistent with that shown in Figure 5The spectrum measured at 120° C. indicated by the dotted line above tends to have substantially the same shape. That is, in the lithium tetraborate crystal, there are no Li defects, and as a result, the elastic modulus is high and plastic deformation is not likely to occur.
[0148] The above solid 7 The measurement conditions of Li-NMR are as follows.
[0149] Specifically, the measurement was performed using a 4 mm HX CP-MAS probe by a single pulse method, 90° pulse width: 3.2 μs, observation frequency: 155.546 MHz, observation width: 1397.6 ppm, repetition time: 15 seconds, integration / integration: 1 time, and MAS rotation speed: 0 Hz.
[0150] <Raman spectroscopy characteristics>
[0151] Furthermore, from the viewpoint of achieving more excellent effects of the present invention, the first specific solid electrolyte preferably satisfies the following requirement 2.
[0152] Requirement 2: The first specific solid electrolyte has a Raman spectrum of 600 to 850 cm -1 The coefficient of determination obtained by linear regression analysis based on the least squares method within the wavenumber region is above 0.9400.
[0153] In view of further improving the effects of the present invention, the coefficient of determination in the requirement 2 is more preferably 0.9600 or more. The upper limit is not particularly limited, and 1.0000 is an example.
[0154] Regarding the above requirement 2, Figure 6 While explaining.
[0155] Regarding requirement 2, first, a Raman spectrum of the first specific solid electrolyte is obtained. As a method for measuring the Raman spectrum, Raman imaging is implemented. Raman imaging refers to microscopic spectroscopy combined with microscopy technology in Raman spectroscopy. Specifically, it is a method of detecting measurement light including Raman scattered light by scanning the excitation light on the sample, and visualizing the distribution of components based on the intensity of the measurement light.
[0156] The measurement conditions for Raman imaging are as follows: the excitation light is 532 nm, the objective lens is 100 times, the mapping method is point scanning, the spacing is 1 μm, the exposure time for each point is 1 second, the accumulation and integration times are 1 time, and the measurement range is 70 μm×50 μm.
[0157] Furthermore, the Raman spectrum data is subjected to principal component analysis (PCA) processing to remove noise. Specifically, in the principal component analysis processing, the spectrum is recombined using components with an autocorrelation coefficient of 0.6 or more.
[0158] Figure 6 An example of the Raman spectrum of the first specific solid electrolyte is shown in FIG.
[0159] exist Figure 6 In the graph shown in , the vertical axis represents the Raman intensity and the horizontal axis represents the Raman shift. Figure 6 The Raman spectrum shown in Figure 600-850 bm -1 In the wave number region, the coefficient of determination (coefficient of determination R) obtained by linear regression analysis based on the least squares method was calculated. 2 ). That is, in Figure 6 The Raman spectrum of 600-850 cm -1 In the wave number region, the regression line is obtained by the least square method ( Figure 6 The coefficient of determination R of the regression line is calculated. 2 In addition, the coefficient of determination takes a value between 0 (no linear correlation) and 1 (complete linear correlation of the measured values) depending on the linear correlation of the measured values.
[0160] In the first specific solid electrolyte, if Figure 6 As shown, at 600-850cm -1 In the wave number region, almost no peak was observed, and as a result, a high determination coefficient was shown.
[0161] In addition, the above determination coefficient R 2 It is equivalent to the square of the correlation coefficient (Pearson product-moment correlation coefficient). More specifically, in this specification, the determination coefficient R 2 The calculation is performed by the following formula: wherein x1 and y1 represent the wave number in the Raman spectrum and the Raman intensity corresponding to the wave number, x2 represents the (additive) average of the wave number, and y2 represents the (additive) average of the Raman intensity.
[0162] [Formula 8]
[0163]
[0164] on the other hand, Figure 7 The Raman spectrum of a typical lithium tetraborate crystal is shown in FIG. Figure 7 As shown, in the case of a general lithium tetraborate crystal, the wavelength of 716 to 726 cm -1 and 771~785cm -1 A peak is observed in the wave number region of .
[0165] When this peak exists, it is between 600 and 850 cm -1 In the wave number region, when the coefficient of determination is calculated by linear regression analysis based on the least squares method, the coefficient of determination is less than 0.9400.
[0166] That is, the determination coefficient being 0.9400 or more means that the first specific solid electrolyte contains almost no crystal structure contained in a general lithium tetraborate crystal. Therefore, it is considered that, as a result, the first specific solid electrolyte has the characteristic of easy plastic deformation and Li + Excellent jumping properties.
[0167] <Bulk elastic modulus>
[0168] The bulk modulus of the first specific solid electrolyte is not particularly limited, but is preferably 50 GPa or less, more preferably 45 GPa or less, and further preferably 40 GPa or less from the viewpoint of achieving a more excellent effect of the present invention. The lower limit is not particularly limited, but is preferably 5 GPa or more.
[0169] The measurement of the bulk modulus is performed by an ultrasonic attenuation method.
[0170] Specifically, first, a suspension obtained by suspending the first specific solid electrolyte in pure water is prepared. The content of the first specific solid electrolyte in the suspension is set to 1.2% by mass relative to the total mass of the suspension. Next, the ultrasonic attenuation spectrum of the above suspension is measured, and the bulk modulus of the first specific solid electrolyte is obtained by fitting based on the scattering attenuation theory formula. In addition, when performing the above fitting, the particle size distribution, density and Poisson's ratio of the first specific solid electrolyte are used.
[0171] Regarding the fitting based on the above-mentioned scattering attenuation theoretical formula, the bulk modulus was calculated using equations (7), (12), and (13) described in Kohjiro Kubo et al., Ultrasonics 62 (2015) pp. 186-194.
[0172] The particle size distribution of the first specific solid electrolyte is obtained by acquiring a particle image using a flow particle image analysis method, calculating the particle size of the first specific solid electrolyte, and preparing a particle size histogram (particle size distribution). The particle size is equivalent to an equivalent circle diameter.
[0173] <X-ray diffraction characteristics>
[0174] The first specific solid electrolyte preferably satisfies the following requirement 3.
[0175] Requirement 3: In the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα rays of the first specific solid electrolyte, there is no first peak having a peak in the range of diffraction angle 2θ of 21.6 to 22.0° and a full width at half maximum of 0.65° or less, no second peak having a peak in the range of 25.4 to 25.8° and a full width at half maximum of 0.65° or less, no third peak having a peak in the range of 33.4 to 33.8° and a full width at half maximum of 0.65° or less, and no fourth peak having a peak in the range of 34.4 to 34.8° and a full width at half maximum of 0.65° or less, or
[0176] When at least one specific peak selected from the first peak, the second peak, the third peak and the fourth peak is present in the X-ray diffraction pattern, the intensity ratio of at least one of the specific peaks calculated by the following intensity measurement method is 5.0 or less.
[0177] Intensity measurement method: Calculate the average intensity 1 in the range of +0.45° to +0.55° from the diffraction angle 2θ of the peak of the specific peak, calculate the average intensity 2 in the range of -0.55° to -0.45° from the diffraction angle 2θ of the peak of the specific peak, calculate the arithmetic mean of the average intensity 1 and the average intensity 2, and set the ratio of the peak intensity in the peak of the specific peak to the arithmetic mean as the intensity ratio.
[0178] Requirement 3 will be described below.
[0179] First, in the X-ray diffraction pattern obtained by X-ray diffraction measurement of the first specific solid electrolyte using CuKα rays, if the first peak with a peak located in the range of 21.6 to 22.0° and a full width at half maximum of less than 0.65°, the second peak with a peak located in the range of 25.4 to 25.8° and a full width at half maximum of less than 0.65°, the third peak with a peak located in the range of 33.4 to 33.8° and a full width at half maximum of less than 0.65°, and the fourth peak with a peak located in the range of 34.4 to 34.8° and a full width at half maximum of less than 0.65° do not exist, requirement 3 is satisfied.
[0180] The full width at half maximum (FWHM) of a peak refers to the width (°) at a point where the intensity of the peak is half of that of the peak.
[0181] Furthermore, when there is at least one specific peak selected from the first peak, the second peak, the third peak and the fourth peak in the X-ray diffraction pattern obtained by the X-ray diffraction measurement using CuKα rays of the first specific solid electrolyte, requirement 3 is also satisfied when the intensity ratio calculated by the intensity measurement method described later of at least one of the specific peaks is less than 5.0.
[0182] The following is a method for measuring strength. Fig.10 Provide explanation.
[0183] Fig.10 This is a diagram showing an example of a specific peak appearing in a diffraction pattern obtained by X-ray diffraction measurement using CuKα rays of the first specific solid electrolyte. Fig.10 In the diffraction pattern shown in FIG. 1 , the intensity of the top peak indicates a specific peak with an intensity of 1. In the intensity measurement method, as Fig.10 As shown, the average intensity 1 in the range of +0.45° to +0.55° is calculated from the diffraction angle 2θ of the top of the specific peak, and the average intensity 2 in the range of -0.55° to -0.45° is further calculated from the diffraction angle 2θ of the top of the specific peak. Next, the arithmetic mean of the average intensity 1 and the average intensity 2 is calculated, and the ratio of the intensity 1 to the arithmetic mean is obtained as the intensity ratio.
[0184] When the above requirement 3 is satisfied, it means that the first specific solid electrolyte does not have a crystal structure or hardly has a crystal structure and is in an amorphous state.
[0185] That is, the 1st to 4th peaks described in requirement 3 are mainly peaks derived from the crystal structure (especially the crystal structure of lithium tetraborate) in the 1st specific solid electrolyte. In the absence of such peaks, it means that in the 1st specific solid electrolyte, there is no prescribed crystal structure and it is in an amorphous state. Moreover, even if at least one of the 1st to 4th peaks exists, the intensity ratio of any one of the specific peaks that exists is less than the prescribed value, which also indicates that there is almost no crystal structure that hinders the effect of the present invention in the 1st specific solid electrolyte. In addition, in the 1st specific solid electrolyte, in addition to the peaks derived from the prescribed crystal structure such as the crystal structure of lithium tetraborate cited as an example, peaks caused by other factors may also be generated. As other factors, for example, peaks derived from specific components (for example, lithium salts) can be cited, and such peaks sometimes overlap with any of the 1st to 4th peaks mentioned above. However, when an amorphous state is achieved, in most cases the 1st to 4th peaks are reduced. Assuming that, as described above, even if a peak due to other main reasons occasionally overlaps with any of the 1st to 4th peaks to form a large peak, the presence of at least one specific peak having an intensity ratio below a specified value can also be regarded as the 1st specific solid electrolyte being an amorphous state with excellent ion conductivity.
[0186] The X-ray diffraction measurement was performed using CuKα rays under the measurement conditions of 0.01° / pitch and 3° / min.
[0187] In the X-ray diffraction spectrum obtained by X-ray diffraction measurement using CuKα rays of the first specific solid electrolyte, it is preferred that the first peak, the second peak, the third peak, and the fourth peak are all absent, or the intensity ratio of at least one of the specific peaks selected from the first peak, the second peak, the third peak, and the fourth peak is 3.0 or less. Among them, it is more preferred that the first peak, the second peak, the third peak, and the fourth peak are all absent, or the intensity ratio of at least one of the specific peaks selected from the first peak, the second peak, the third peak, and the fourth peak is 2.0 or less.
[0188] <Particle size>
[0189] The particle size of the first specific solid electrolyte is not particularly limited. From the viewpoint of achieving more excellent effects of the present invention, the median particle size (D50) of the first specific solid electrolyte is preferably 0.01 to 20 μm, and more preferably 0.1 to 2.0 μm.
[0190] The median particle size (D50) can be obtained by using a flow particle image analysis method to obtain a particle image, and calculating the particle size of the first specific solid electrolyte, and calculating the particle size distribution made by the calculated particle size, and obtaining the particle size in which the total volume of the particles on the large diameter side and the small diameter side is equal. In addition, the above particle size is equivalent to the equivalent circle diameter.
[0191] <Ion conductivity>
[0192] The ion conductivity of the first specific solid electrolyte is not particularly limited, but is preferably 1.0×10 -6 S / cm or more, more preferably 1.0×10 -5 S / cm or more. The upper limit is not particularly limited, but in most cases it is 1.0×10 -3 S / cm or less.
[0193] In this specification, the ionic conductivity (ionic conductivity) of the solid electrolyte is measured by the following method. First, two Au electrodes are arranged in a manner to sandwich the solid electrolyte (solid electrolyte molded body). Under the conditions of a measurement temperature of 25°C and an applied voltage of 100mV, the AC impedance between the two Au electrodes is measured in a measurement frequency range of 1Hz to 1MHz, and the ionic conductivity of the solid electrolyte is calculated by analyzing the arc diameter of the obtained Cole-Cole diagram (Nyquist diagram).
[0194] [Oxide Solid Electrolyte (Second Embodiment)]
[0195] As a second embodiment of the present invention, the following oxide solid electrolytes can be mentioned.
[0196] The oxide solid electrolyte of the present embodiment contains Li, B, O, and X, and satisfies the following requirements A-1 and A-2.
[0197] X represents at least one element selected from F, Cl, Br, I, S, N, H, Se, Te, C, P, Si, Al, Ga, In, Ge, As, Sb and Sn.
[0198] Requirement A-1: In the reduced two-body distribution function G(r) obtained from the X-ray total scattering measurement of the oxide solid electrolyte, there is a peak located at r. The first peak and the top peak in the range of r are The second peak in the range of , the G(r) of the top of the first peak and the G(r) of the top of the second peak are greater than 1.0.
[0199] Requirement A-2: In the reduced two-body distribution function G(r) obtained from the X-ray total scattering measurement of the oxide solid electrolyte, when r is greater than And for In the following range, the absolute value of G(r) is less than 1.0.
[0200] The present inventors have found that when the oxide solid electrolyte contains the element X in addition to Li, B and O and further satisfies the above-mentioned requirements A-1 and A-2, it exhibits an excellent effect of improving ion conductivity.
[0201] When the oxide solid electrolyte containing Li, B, O and element X satisfies requirements A-1 and A-2, the oxide solid electrolyte itself shows elastic properties that are softer and easier to plastically deform than the previous lithium-containing oxides because it has a short-range ordered structure related to the interatomic distance of BO and BB, but has almost no long-range ordered structure. As a result, it is speculated that in the molded body of the oxide solid electrolyte formed by pressure treatment, the adhesion between the oxide solid electrolytes and / or the adhesion between the oxide solid electrolyte and other ion conductors is improved, and the interface resistance can be reduced, so that more excellent ion conductivity can be obtained.
[0202] Hereinafter, the oxide solid electrolyte of the present embodiment is also described as a “second specific solid electrolyte”.
[0203] The element composition of the second specific solid electrolyte contains Li, B, O, and the element X, and is not particularly limited as long as requirements A-1 and A-2 are satisfied.
[0204] The element X is at least one selected from F, Cl, Br, I, S, N, H, Se, Te, C, P, Si, Al, Ga, In, Ge, As, Sb and Sn. The second specific solid electrolyte may contain only one element X, or may contain two or more elements X.
[0205] The second specific solid electrolyte preferably contains at least F, Cl, Br, I, S, N, Se, or Te as the element X.
[0206] When the second specific solid electrolyte contains only one element X, the element is preferably X, F, Cl, or I, more preferably Cl or I, and further preferably I.
[0207] When the second specific solid electrolyte contains two or more elements X, the element X preferably contains at least one selected from F, Cl, Br, I, Se, Te and H and at least one selected from C, P, S and N, and more preferably contains at least one selected from F, Cl and I and at least one selected from S and N.
[0208] Among them, when the second specific solid electrolyte contains two or more elements X, the element X is more preferably an embodiment containing F and at least one selected from S and N, and the element X is particularly preferably an embodiment containing F, S, and N.
[0209] As the second specific solid electrolyte, a compound represented by the following general formula (II) is preferred.
[0210] Li a B b O c X d (II)
[0211] X in the general formula (II) is the above-mentioned element X. a to d represent the molar number of each element, a is 1.75<a<2.45, b is 3.75<b<4.25, c is 6.50<c<10.00, and d represents the total molar number of the elements represented by X, which is 0<d<0.50.
[0212] From the viewpoint of further improving the effect of the present invention, a is preferably 1.75<a<2.25, and more preferably 1.90<a<2.10.
[0213] b is preferably 3.90<b<4.10, more preferably b=4.00.
[0214] c is preferably 6.50<c<10.00, more preferably 7.00<c<9.80.
[0215] d is preferably 0<d<0.40, more preferably 0<d<0.20.
[0216] The type and content of each element contained in the second specific solid electrolyte can be identified by the elemental analysis method of the first specific solid electrolyte described above.
[0217] The physical properties and structure other than requirements A-1 and A-2 of the second specific solid electrolyte, including preferred embodiments thereof, are the same as those of the first specific solid electrolyte.
[0218] Hereinafter, unless otherwise specified, the first specific solid electrolyte and the second specific solid electrolyte are not distinguished and are described together. Furthermore, both the first specific solid electrolyte and the second specific solid electrolyte are also collectively referred to as a “specific solid electrolyte”.
[0219] [Method for producing a specific solid electrolyte]
[0220] The method for producing the specific solid electrolyte is not particularly limited as long as it is a method for producing a composite oxide having the composition represented by the above-mentioned general formula (I) and exhibiting the above-mentioned characteristics.
[0221] Among them, from the viewpoint of being able to produce a specific solid electrolyte with good productivity, a production method having a step of mechanically grinding a lithium tetraborate compound in the presence of an element source containing at least one element X (hereinafter also referred to as a "specific element source") is preferred.
[0222] The lithium tetraborate compound is a compound represented by Li2B4O7 and is composed of Li, B and O, but may deviate from the above standard value. More specifically, lithium tetraborate as a raw material of the specific solid electrolyte is preferably Li 2+x B 4+y O 7+z A compound represented by (-0.3<x<0.3, -0.3<y<0.3, -0.3<z<0.3).
[0223] Furthermore, the lithium tetraborate compound is preferably a lithium tetraborate crystal (LBO crystal). The LBO crystal refers to a lithium tetraborate compound in which an XRD pattern belonging to the space group I41cd is observed when XRD measurement is performed.
[0224] The specific element source contains at least one element X. The specific element source may be composed of one compound containing the element X, or may be composed of two or more compounds. The specific element source preferably contains at least one of the preferred elements X described above.
[0225] As the specific element source, a salt is preferred, and a lithium salt is more preferred.
[0226] Examples of the lithium salt include LiN(SO 2 F) 2 (lithium bis(fluorosulfonyl)imide, LiFSI), LiI, LiCl, and LiF.
[0227] The usage amount of the specific element source is not particularly limited, and is appropriately adjusted in order to obtain a specific solid electrolyte.
[0228] The amount of the specific element source used is preferably 1 to 40 parts by mass, more preferably 5 to 20 parts by mass, based on 100 parts by mass of the lithium tetraborate compound.
[0229] Mechanical grinding is a process of pulverizing a sample while applying mechanical energy.
[0230] As mechanical grinding treatment, for example, a ball mill, a vibration mill, a turbine mill and a disc mill can be mentioned. From the viewpoint of being able to produce a specific solid electrolyte with good productivity, a ball mill is preferred. As a ball mill, for example, a vibration ball mill, a rotary ball mill and a planetary ball mill can be mentioned, and a planetary ball mill is more preferred.
[0231] As the conditions for the ball milling treatment, appropriate conditions can be selected according to the raw materials used.
[0232] The material of the grinding balls (medium) used in the ball milling is not particularly limited, and examples thereof include agate, silicon nitride, zirconium oxide, aluminum oxide, and iron-based alloys. From the viewpoint of being able to produce a specific solid electrolyte with good productivity, zirconium oxide is preferred.
[0233] The average particle size of the grinding balls is not particularly limited. From the perspective of being able to produce a specific solid electrolyte with good productivity, it is preferably 1 to 10 mm, and more preferably 3 to 7 mm. The above average particle size is obtained by measuring the diameters of any 50 grinding balls and averaging them. When the grinding balls are not spherical, the major diameter is set as the diameter.
[0234] The number of grinding balls used in ball milling is not particularly limited, but is preferably 10 to 100, more preferably 40 to 60, from the viewpoint of being able to produce the specific solid electrolyte with good productivity.
[0235] The material of the grinding pot used in the ball milling is not particularly limited, and examples thereof include agate, silicon nitride, zirconium oxide, aluminum oxide, and iron-based alloys. From the viewpoint of being able to produce a specific solid electrolyte with good productivity, zirconium oxide is preferred.
[0236] The rotation speed during ball milling is not particularly limited, but is preferably 200 to 700 rpm, more preferably 350 to 550 rpm, from the viewpoint of being able to produce a specific solid electrolyte with good productivity.
[0237] The treatment time of the ball mill is not particularly limited, but is preferably 10 to 200 hours, more preferably 20 to 140 hours, from the viewpoint of being able to produce the specific solid electrolyte with good productivity.
[0238] The ball milling may be performed in the air or in an inert gas (eg, argon, helium, or nitrogen) atmosphere.
[0239] As a method for producing a specific solid electrolyte, a method having the following step 1, step 2, and step 3 is preferred from the viewpoint of preferably mixing additives.
[0240] Step 1: A step of mechanically grinding lithium tetraborate crystals.
[0241] Step 2: A step of adding a specific element source to the micronized lithium tetraborate compound obtained in step 1.
[0242] Step 3: A step of further subjecting the lithium tetraborate compound to mechanical milling in the presence of a specific element source.
[0243] Preferred conditions for the mechanical polishing treatment in the above-mentioned step 1 and step 3 are the same as those described above except for the treatment time.
[0244] In steps 1 and 3, when a ball mill is used for mechanical grinding, the processing time of the ball mill is not particularly limited. From the perspective of being able to produce a specific solid electrolyte with good productivity, in step 1, it is preferably 0.5 to 100 hours, more preferably 2 to 50 hours, and in step 3, it is preferably 0.5 to 100 hours, more preferably 2 to 50 hours.
[0245] In step 2, the specific element source may be added once or added in multiple portions while performing mechanical milling.
[0246] [Specified solid electrolyte molded body]
[0247] The molded body of the specific solid electrolyte (hereinafter, also referred to as “specific molded body”) is formed using the above-mentioned specific solid electrolyte.
[0248] The method for forming the specific molded body is not particularly limited, and for example, a method of forming the molded body by subjecting the specific solid electrolyte to a pressure treatment may be mentioned. That is, the specific molded body is preferably formed by subjecting the specific solid electrolyte to a pressure treatment (pressure molding process).
[0249] Hereinafter, the above-mentioned pressure treatment method will be described in detail.
[0250] The method of the pressure treatment is not particularly limited, and a method using a known pressurizing device may be mentioned.
[0251] The pressure applied during the pressure treatment is not particularly limited, and the optimum pressure is appropriately selected according to the components in the specific solid electrolyte. However, from the viewpoint of achieving more excellent effects of the present invention, the pressure is preferably 5 to 1500 MPa, and more preferably 10 to 600 MPa.
[0252] The time of the pressurization treatment is not particularly limited, but is preferably 0.01 to 0.5 hours, more preferably 0.1 to 0.2 hours, from the viewpoint of more excellent effects of the present invention and productivity.
[0253] Furthermore, during the pressure treatment, a heat treatment may be performed. The heating temperature during the heat treatment is not particularly limited, but is preferably 40 to 400° C., more preferably 200 to 350° C. The heating time during the heat treatment is preferably 1 minute to 6 hours.
[0254] The atmosphere during the pressurization process is not particularly limited, and examples thereof include atmospheric air, dry air (dew point -20°C or lower), and an inert gas (for example, argon, helium, and nitrogen) atmosphere.
[0255] The specific molded body may be a composite body containing a specific solid electrolyte and other components other than the specific solid electrolyte. As other components contained in the specific molded body, for example, an ion conductivity of 1.0×10 -6 S / cm or more lithium compound (hereinafter also referred to as "second lithium compound") and a binder.
[0256] The specific molded body preferably contains a second lithium compound. Since the specific molded body contains the second lithium compound, the ion conductivity of the specific molded body is further improved.
[0257] The type of the second lithium compound is not particularly limited as long as the ion conductivity at 25°C is 1.0×10 -6 S / cm or more. The ion conductivity of the second lithium compound at 25°C is preferably 1.0×10 -5 S / cm or more. The upper limit is not particularly limited, but in most cases it is 1.0×10 -3 S / cm or less.
[0258] The ion conductivity of the second lithium compound can be measured according to the above-mentioned method for measuring the ion conductivity of the solid electrolyte.
[0259] Examples of the second lithium compound include the following compounds 1 to 9.
[0260] Compound 1: A lithium compound having a garnet structure or a garnet-like structure containing at least Li, La, Zr and O
[0261] Compound 2: A lithium compound having a perovskite structure containing at least Li, Ti, La and O
[0262] Compound 3: contains at least Li, M 1 , P and O, M 1 A lithium compound representing at least one of Ti, Zr, Si and Ge and having a NASICON structure
[0263] Compound 4: A lithium compound having an amorphous structure containing at least Li, P, O and N
[0264] Compound 5: A lithium compound having a monoclinic structure containing at least Li, Si and O
[0265] Compound 6: LiM 2 X 1 O4 means, M 2 Indicates a divalent element or a trivalent element, in M 2 In the case of a divalent element, X 1 Represents a pentavalent element, in M 2 In the case of a trivalent element, X 1 It represents a tetravalent element and is a lithium compound having an olivine structure.
[0266] In addition, as the above M 2 Examples of the divalent element represented by include Mg, Ca, Sr, Ba and Zn. 2 Examples of the trivalent element represented by include Al, Ga, In, Sc, Nd and Tm. 1 The pentavalent element represented by X includes, for example, P, As and Sb. 1 Examples of the tetravalent element represented by include Si and Ge.
[0267] Compound 7: Contains at least Li, O and X 2 , X 2 A lithium compound representing at least one of Cl, Br, N and I and having an antiperovskite structure
[0268] Compound 8: Li2M 3 Y4 means, M 3 A lithium compound in which R represents at least one of Cd, Mg, Mn and V, Y represents at least one of F, Cl, Br and I, and the compound has a spinel structure.
[0269] Compound 9: a lithium compound having a β-alumina structure.
[0270] The bulk modulus of the second lithium compound is not particularly limited, but is preferably 50 to 300 GPa, more preferably 60 to 200 GPa, from the viewpoint of achieving more excellent effects of the present invention.
[0271] The method for measuring the above-mentioned bulk modulus is the same as the method for measuring the bulk modulus of the specific solid electrolyte.
[0272] The average particle size of the second lithium compound is not particularly limited, but is preferably 0.1 to 100 μm, more preferably 1 to 20 μm, from the viewpoint of achieving more excellent effects of the present invention.
[0273] The method for measuring the average particle size is the same as the method for measuring the average particle size of the specific solid electrolyte.
[0274] The second lithium compound can be produced by a known method, or a commercially available product can be used.
[0275] The content of the second lithium compound in the specific molded body is not particularly limited, but is preferably 50 to 99 mass %, more preferably 80 to 98 mass %, relative to the total mass of the specific molded body from the viewpoint of better effects of the present invention and easier plastic deformation of the specific molded body.
[0276] There is no particular restriction on the mixing ratio of the specific solid electrolyte and the second lithium compound in the specific molded body. From the perspective of better ion conductivity, the mass ratio of the content of the specific solid electrolyte to the content of the second lithium compound (content of the specific solid electrolyte / content of the second lithium compound) is preferably greater than 1 / 2, and more preferably greater than 4 / 5.
[0277] The specific molded body may contain a binder. Examples of the binder include various organic high molecular compounds (polymers).
[0278] The organic polymer compound constituting the binder may be in a particulate form or a non-particulate form. The particle size (volume average particle size) of the particulate binder is preferably 10 to 1000 nm, more preferably 20 to 750 nm, further preferably 30 to 500 nm, and particularly preferably 50 to 300 nm.
[0279] The type of the binder contained in the specific molded product is not particularly limited, and examples thereof include the following polymers.
[0280] Examples of the fluorine-containing polymer include polytetrafluoroethylene, polyvinylidene fluoride, and a copolymer of polyvinylidene fluoride and hexafluoropropylene.
[0281] Examples of the hydrocarbon-based thermoplastic polymer include polyethylene, polypropylene, styrene butadiene rubber, hydrogenated styrene butadiene rubber, butene rubber, acrylonitrile butadiene rubber, polybutadiene, and polyisoprene.
[0282] Examples of the acrylic polymer include various (meth)acrylic acid monomers, (meth)acrylamide monomers, and copolymers of monomers constituting these polymers (preferably a copolymer of acrylic acid and methyl acrylate).
[0283] Furthermore, copolymers (copolymers) with other vinyl monomers, for example, copolymers of methyl (meth)acrylate and styrene, copolymers of methyl (meth)acrylate and acrylonitrile, and copolymers of butyl (meth)acrylate, acrylonitrile, and styrene are also preferably used.
[0284] Examples of other polymers include polyurethane, polyurea, polyamide, polyimide, polyester, polyether, polycarbonate, and cellulose derivatives.
[0285] Among them, acrylic polymer, polyurethane, polyamide or polyimide is preferred.
[0286] As the polymer constituting the binder, a polymer synthesized by a conventional method may be used, or a commercially available product may be used.
[0287] The binder may be used alone or in combination of two or more.
[0288] When the specific molded product contains a binder, the content of the binder is preferably 0.1 to 3% by mass, more preferably 0.5 to 1% by mass, based on the total mass of the specific molded product.
[0289] The specific molded body may contain other lithium compounds in addition to the specific solid electrolyte and the second lithium compound.
[0290] The other lithium compound is not particularly limited, and examples thereof include lithium salts described in paragraphs 0082 to 0085 of JP-A-2015-088486.
[0291] When the specific molded body contains a lithium salt, the content of the lithium salt is preferably 0.1 to 3 mass %, more preferably 0.5 to 1 mass %, based on the total mass of the specific molded body.
[0292] Furthermore, the specific molded body may contain other solid electrolytes in addition to the specific solid electrolyte and the second lithium compound.
[0293] The ion conductivity of the fixed molded body is not particularly limited, but is preferably 1.0×10 -6 S / cm or more, more preferably 1.0×10 -5 S / cm or more.
[0294] The method for measuring the ion conductivity of the specific molded body is the same as the method for measuring the ion conductivity of the specific solid electrolyte.
[0295] 〔use〕
[0296] The above-mentioned specific solid electrolyte can be used for various purposes.
[0297] For example, it can be used in various batteries (for example, all-solid-state secondary batteries, solid oxide fuel cells, and batteries using solid oxide steam electrolysis). Among them, the specific solid electrolyte is preferably used in all-solid-state secondary batteries.
[0298] More specifically, the specific solid electrolyte is preferably used as a solid electrolyte contained in a solid electrolyte layer, a positive electrode active material layer, and a negative electrode active material layer in an all-solid-state secondary battery.
[0299] <Solid Electrolyte Layer-Forming Composition>
[0300] The specific solid electrolyte is preferably used as a component of the solid electrolyte layer-forming composition. That is, the solid electrolyte layer-forming composition contains the above-mentioned specific solid electrolyte.
[0301] The specific solid electrolyte contained in the solid electrolyte layer-forming composition is as described above.
[0302] The solid electrolyte layer-forming composition may contain other components in addition to the specific solid electrolyte.
[0303] Examples of other components include the above-mentioned binder and lithium salt.
[0304] The composition for forming a solid electrolyte layer may contain other solid electrolytes in addition to the specific solid electrolyte. Other solid electrolytes refer to solid electrolytes that can move ions inside them. As solid electrolytes, inorganic solid electrolytes are preferred. Since inorganic solid electrolytes are generally solid in a stable state, they are usually not dissociated or freed into cations and anions.
[0305] Examples of other solid electrolytes include sulfide-based inorganic solid electrolytes, oxide-based inorganic solid electrolytes other than specific solid electrolytes, halide-based inorganic solid electrolytes, and hydride-based solid electrolytes.
[0306] Furthermore, the solid electrolyte layer-forming composition may contain a dispersion medium.
[0307] As the dispersion medium, for example, various organic solvents can be mentioned. As the organic solvent, alcohol compounds, ether compounds, amide compounds, amine compounds, ketone compounds, aromatic compounds, aliphatic compounds, nitrile compounds and ester compounds can be mentioned. Among them, ether compounds, ketone compounds, aromatic compounds, aliphatic compounds or ester compounds are preferred.
[0308] The boiling point of the dispersion medium at normal pressure (1 atmosphere) is preferably 50° C. or higher, more preferably 70° C. or higher. The upper limit is preferably 250° C. or lower, more preferably 220° C. or lower.
[0309] The above-mentioned dispersion media may be used alone or in combination of two or more.
[0310] The content of the dispersion medium in the solid electrolyte layer-forming composition is not particularly limited, but is preferably 20 to 99% by mass, more preferably 25 to 70% by mass, based on the total mass of the solid electrolyte layer-forming composition.
[0311] The method for forming a solid electrolyte layer using the solid electrolyte layer-forming composition is not particularly limited, and an example includes a method in which the solid electrolyte layer-forming composition is applied and the formed coating film is subjected to a pressure treatment.
[0312] The method for applying the solid electrolyte layer-forming composition is not particularly limited, and examples thereof include spray coating, spin coating, dip coating, slit coating, spray coating, aerosol deposition, thermal spraying, and bar coating.
[0313] In addition, after applying the solid electrolyte layer-forming composition, the obtained coating film may be dried as needed. The drying temperature is not particularly limited, but as a lower limit, it is preferably 30° C. or higher, more preferably 60° C. or higher, and further preferably 80° C. or higher. As an upper limit of the drying temperature, it is preferably 300° C. or lower, and more preferably 250° C. or lower.
[0314] The method of pressurizing the coating film is not particularly limited, and examples thereof include a method using a known pressurizing device (for example, a hydraulic cylinder press).
[0315] The pressure applied during the pressurization treatment is not particularly limited, but is preferably 5 to 1500 MPa, more preferably 300 to 600 MPa, from the viewpoint of obtaining a more excellent ion conductor in the formed solid electrolyte layer.
[0316] The time of the pressurization treatment is not particularly limited, but is preferably 1 minute to 6 hours, more preferably 1 to 20 minutes, from the viewpoint of obtaining a more excellent ion conductor in the formed solid electrolyte layer and from the viewpoint of productivity.
[0317] Furthermore, during the pressure treatment, a heat treatment may be performed. The heating temperature during the heat treatment is not particularly limited, but is preferably 30 to 300° C., and the heating time is more preferably 1 minute to 6 hours.
[0318] The atmosphere during the pressurization process is not particularly limited, and examples thereof include atmospheric air, dry air (dew point -20°C or lower), and an inert gas (for example, argon, helium, and nitrogen) atmosphere.
[0319] (Solid electrolyte layer)
[0320] One of the preferred aspects of the solid electrolyte layer is a solid electrolyte layer formed using the above-mentioned solid electrolyte layer-forming composition and containing a specific solid electrolyte.
[0321] The content of the specific solid electrolyte in the solid electrolyte layer is not particularly limited, and is preferably 50% by mass or more, more preferably 80% by mass or more, relative to the total mass of the solid electrolyte layer. The upper limit is not particularly limited, and may be 100% by mass relative to the solid electrolyte layer.
[0322] The solid electrolyte layer may contain components other than the specific solid electrolyte. Examples of the above components include components that may be contained in the above composition for forming a solid electrolyte layer excluding the dispersion medium.
[0323] <Active Material Layer-Forming Composition>
[0324] The specific solid electrolyte is preferably used as a component of the active material layer-forming composition. That is, the active material layer-forming composition contains the above-mentioned specific solid electrolyte. In addition, the "active material layer" means a layer selected from the negative electrode active material layer and the positive electrode active material layer.
[0325] The active material layer-forming composition contains at least the above-mentioned specific solid electrolyte and an active material.
[0326] The mixing ratio of the specific solid electrolyte and the active material in the active material layer-forming composition is not particularly limited, and the mass ratio of the specific solid electrolyte content to the active material content (specific solid electrolyte / active material) is not particularly limited, but is preferably 0.01 to 50, and more preferably 0.05 to 20.
[0327] The specific solid electrolyte contained in the active material layer-forming composition is as described above.
[0328] Examples of the active material include negative electrode active materials and positive electrode active materials. The active material will be described in detail below.
[0329] (Negative electrode active material)
[0330] The negative electrode active material is preferably capable of reversibly inserting or releasing lithium ions or the like. The negative electrode active material is not particularly limited as long as it has the above-mentioned function, and examples thereof include carbonaceous materials, oxides of metals or metalloid elements, lithium monomers, lithium alloys, and negative electrode active materials capable of forming alloys with lithium.
[0331] The carbonaceous material used as the negative electrode active material refers to a material substantially composed of carbon. For example, carbon black such as petroleum pitch, acetylene black (AB), graphite (natural graphite and artificial graphite such as vapor-grown graphite), and various synthetic resins such as PAN (polyacrylonitrile) resin or furfuryl alcohol resin can be calcined.
[0332] In addition, various carbon fibers such as PAN-based carbon fibers, cellulose-based carbon fibers, pitch-based carbon fibers, vapor-grown carbon fibers, dehydrated PVA (polyvinyl alcohol)-based carbon fibers, lignin carbon fibers, glassy carbon fibers, and activated carbon fibers, as well as mesophase microspheres, graphite whiskers, and flat graphite can also be cited.
[0333] These carbonaceous materials can be further divided into carbonaceous materials that are not easily graphitized (also called hard carbon) and graphite-based carbonaceous materials according to the degree of graphitization.
[0334] And, the carbonaceous material preferably has the interplanar spacing, density or crystallite size recorded in Japanese Patent Laid-Open No. 62-022066, Japanese Patent Laid-Open No. 2-006856 and Japanese Patent Laid-Open No. 3-045473. The carbonaceous material need not be a single material, and a mixture of natural graphite and artificial graphite recorded in Japanese Patent Laid-Open No. 5-090844 and graphite with a coating layer recorded in Japanese Patent Laid-Open No. 6-004516 can also be used.
[0335] As the carbonaceous material, hard carbon or graphite is preferred, and graphite is more preferred.
[0336] The oxide of the metal element or semi-metal element applicable as the negative electrode active material is not particularly limited as long as it is an oxide capable of absorbing and releasing ions such as lithium, and examples thereof include oxides of metal elements (metal oxides), composite oxides of metal elements, composite oxides of metal elements and semi-metal elements, and oxides of semi-metal elements (semi-metal oxides). In addition, composite oxides of metal elements and composite oxides of metal elements and semi-metal elements are also collectively referred to as metal composite oxides.
[0337] As the metal composite oxide, an amorphous oxide is preferred, and a chalcogenide which is a reaction product of a metal element and an element of Group 16 of the periodic table is also preferred.
[0338] In this specification, metalloid elements refer to elements showing properties intermediate between metal elements and non-metal elements, and generally include six elements of boron, silicon, germanium, arsenic, antimony and tellurium, and further include three elements of selenium, polonium and astatine.
[0339] Furthermore, amorphous means that the X-ray diffraction method using CuKα rays has a broad scattering band with a vertex in the region of 20 to 40° at a 2θ value, and may also have crystalline diffraction lines. The strongest intensity of the crystalline diffraction lines observed within 40 to 70° at a 2θ value is preferably 100 times or less, more preferably 5 times or less, and further preferably has no crystalline diffraction line intensity at the vertex of the broad scattering band observed within 20 to 40° at a 2θ value.
[0340] Among the compound group composed of the above-mentioned amorphous oxides and chalcogenides, amorphous oxides of semimetallic elements or the above-mentioned chalcogenides are more preferred, and oxides or chalcogenides composed of one element selected from Groups 13 (IIIB) to 15 (VB) of the periodic table (for example, Al, Ga, Si, Sn, Ge, Pb, Sb and Bi) alone or in combination (composite) of two or more of these are further preferred.
[0341] As amorphous oxides and chalcogenides, preferred are Ga2O3, GeO, PbO, PbO2, Pb2O3, Pb2O4, Pb3O4, Sb2O3, Sb2O4, Sb2O8Bi2O3, Sb2O8Si2O3, Sb2O5, Bi2O3, Bi2O4, GeS, PbS, PbS2, Sb2S3 or Sb2S5.
[0342] As negative electrode active materials that can be used together with the amorphous oxide negative electrode active materials centered on Sn, Si or Ge, carbonaceous materials, lithium monomers, lithium alloys that can occlude and / or release lithium ions or lithium metals, or negative electrode active materials that can form alloys with lithium are preferred.
[0343] From the viewpoint of high current density charge and discharge characteristics, the oxide of a metal element or a semi-metal element (particularly, a metal (complex) oxide) and the above-mentioned chalcogenide preferably contain at least one of titanium and lithium as a constituent component.
[0344] Examples of the metal composite oxide containing lithium (lithium composite metal oxide) include composite oxides of lithium oxide and the above-mentioned metal oxides, the above-mentioned metal composite oxides or the above-mentioned chalcogenides. More specifically, Li2SnO2 can be mentioned.
[0345] The negative electrode active material (eg, metal oxide) also preferably contains titanium element (titanium oxide). Specifically, since Li4Ti5O 12 (Lithium titanate [LTO]) has a small volume change when absorbing and releasing lithium ions, and therefore has excellent rapid charge and discharge characteristics, and is preferred from the viewpoint of being able to increase the life of an all-solid-state secondary battery with suppressed electrode degradation.
[0346] The lithium alloy used as the negative electrode active material is not particularly limited as long as it is an alloy commonly used as a negative electrode active material for all-solid-state lithium ion secondary batteries, and examples thereof include lithium aluminum alloys.
[0347] The negative electrode active material that can form an alloy with lithium is not particularly limited as long as it is a material commonly used as a negative electrode active material for an all-solid-state secondary battery. As the above-mentioned negative electrode active material, negative electrode active materials (alloys) containing silicon or tin elements and metals such as Al and In can be cited, preferably containing silicon elements that can achieve higher battery capacity as negative electrode active materials (active materials containing silicon elements), and more preferably containing silicon elements The content of silicon elements is more than 50mol% of all constituent elements.
[0348] Generally speaking, the negative electrode containing these negative electrode active materials (for example, the Si negative electrode containing the active material containing the silicon element, the Sn negative electrode containing the active material containing the tin element) can absorb more Li ions compared with the carbon negative electrode (graphite and acetylene black, etc.). That is, the absorption amount of Li ions per unit mass increases. As a result, the battery capacity can be increased. As a result, it has the advantage of being able to extend the battery driving time.
[0349] As active materials containing silicon elements, for example, silicon materials such as Si and SiOx (0<x≤1) can be cited, and alloys containing silicon (for example, LaSi2, VSi2, La-Si, Gd-Si and Ni-Si) or organized active materials (for example, LaSi2 / Si) containing titanium, vanadium, chromium, manganese, nickel, copper or lanthanum can be cited. In addition, active materials containing silicon elements and tin elements such as SnSiO3 and SnSiS3 can be cited. In addition, with regard to SiOx, it can be used as a negative electrode active material (metallic oxide) by itself, and since Si is generated by driving an all-solid-state secondary battery, it can be used as a negative electrode active material (its precursor material) that can form an alloy with lithium.
[0350] Examples of the negative electrode active material containing the tin element include active materials containing Sn, SnO, SnO 2 , SnS, SnS 2 , and the above-mentioned silicon element and tin element.
[0351] From the viewpoint of improving battery capacity, the negative electrode active material is preferably a negative electrode active material that can form an alloy with lithium, more preferably the above-mentioned silicon material or an alloy containing silicon (alloy containing silicon element), and further preferably silicon (Si) or an alloy containing silicon.
[0352] The shape of the negative electrode active material is not particularly limited, but preferably particulate. The volume average particle size of the negative electrode active material is not particularly limited, but preferably 0.1 to 60 μm, more preferably 0.5 to 20 μm, and further preferably 1.0 to 15 μm.
[0353] The volume average particle size is measured by the following procedure.
[0354] Use water (heptane if it is a substance unstable in water) to dilute a dispersion of 1 mass % of the negative electrode active material in a 20 mL sample bottle. After irradiating the diluted dispersion sample with 1 kHz ultrasonic waves for 10 minutes, use it in the test immediately. Using this dispersion sample and using a laser diffraction / scattering particle size distribution measuring device, a quartz cell for measurement is used at a temperature of 25°C and data is obtained 50 times to obtain the volume average particle size. For other detailed conditions, refer to the description in JIS Z 8828:2013 "Particle Size Analysis-Dynamic Light Scattering Method" as needed. Make 5 samples for each level and use their average value.
[0355] The negative electrode active material may be used alone or in combination of two or more.
[0356] At least a portion of the surface of the negative electrode active material may be covered with a covering layer including a surface covering agent composed of another metal oxide.
[0357] As the surface covering agent, metal oxides containing Ti, Nb, Ta, W, Zr, Al, Si or Li can be cited. Specifically, titanate spinel, tantalum oxides, niobium oxides and lithium niobate compounds can be cited. Specifically, Li4Ti5O 12 , Li2Ti2O5, LiTaO3, LiNbO3, LiAlO2, Li2ZrO3, Li2WO4, Li2TiO3, Li2B4O7, Li3PO4, Li2MoO4, Li3BO3, LiBO2, Li2CO3, Li2SiO3, SiO2, TiO2, ZrO2, Al2O3 and B2O3.
[0358] One of the preferred aspects of the negative electrode active material is an aspect in which at least a part of the surface of the negative electrode active material is covered with a covering layer containing a specific solid electrolyte.
[0359] The thickness of the coating layer containing the solid electrolyte possessed by the negative electrode active material is not particularly limited, and is, for example, 5 nm to 10 μm.
[0360] The method of forming a coating layer on the surface of a negative electrode active material can be applied to any method of forming a coating layer on the surface of a positive electrode active material described later.
[0361] Furthermore, the surface of the electrode including the negative electrode active material may be surface-treated with sulfur or phosphorus.
[0362] Furthermore, the surface of the particles of the negative electrode active material may be subjected to a surface treatment using active light or active gas (for example, plasma) before or after the above-mentioned surface coating.
[0363] (Positive electrode active material)
[0364] The positive electrode active material is preferably a material that can reversibly insert or release lithium ions or the like. The positive electrode active material is not particularly limited as long as it has the above-mentioned function, but is more preferably a transition metal oxide, and more preferably contains a transition metal element M a (one or more elements selected from Co, Ni, Fe, Mn, Cu and V) transition metal oxide. In addition, the element M may be mixed in the transition metal oxide. b (Metals other than lithium, such as elements of Group 1 (Ia) and Group 2 (IIa) in the periodic table, Al, Ga, In, Ge, Sn, Pb, Sb, Bi, Si, P, and B.) As the mixing amount, it is preferably 2.5 to 3.5 relative to the transition metal element M. a The amount of Li / M is preferably 0 to 30 mol%. a The synthesis was performed by mixing the two components in a molar ratio of 0.3 to 2.2.
[0365] As specific examples of transition metal oxides, there can be cited (MA) transition metal oxides having a layered rock salt structure, (MB) transition metal oxides having a spinel structure, (MC) transition metal phosphate compounds containing lithium, (MD) transition metal halide phosphate compounds containing lithium, and (ME) transition metal silicate compounds containing lithium. Among them, (MA) preferably has a transition metal oxide having a layered rock salt structure, more preferably LiCoO2 or LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2.
[0366] Examples of transition metal oxides (MA) having a layered rock salt structure include LiCoO2 (lithium cobalt oxide [LCO]), LiNi2O2 (lithium nickel oxide), LiNi 0.85 Co 0.10 Al 0.05 O2 (nickel cobalt aluminum oxide [NCA]), LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (lithium nickel manganese cobalt oxide [NMC]) and LiNi 0.5 Mn 0.5 O2 (lithium manganese nickel oxide).
[0367] Examples of the transition metal oxide (MB) having a spinel structure include LiMn2O4 (LMO), LiCoMnO4, Li2FeMn3O8, Li2CuMn3O8, Li2CrMn3O8, and Li2NiMn3O8.
[0368] Examples of lithium-containing transition metal phosphate compounds (MC) include olivine-type iron phosphates such as LiFePO4 and Li3Fe2(PO4)3, iron pyrophosphates such as LiFeP2O7, cobalt phosphates such as LiCoPO4, and Li3V2(PO4)3. ( Monoclinic NASICON type vanadium phosphate salts such as lithium vanadium phosphate.
[0369] Examples of the lithium-containing transition metal halogenated phosphoric acid compound (MD) include iron fluorophosphates such as Li2FePO4F, manganese fluorophosphates such as Li2MnPO4F, and cobalt fluorophosphates such as Li2CoPO4F.
[0370] Examples of the lithium-containing transition metal silicate compound (ME) include Li 2 FeSiO 4 , Li 2 MnSiO 4 , and Li 2 CoSiO 4 .
[0371] The shape of the positive electrode active material is not particularly limited, and is preferably in the form of particles. The volume average particle size of the positive electrode active material is not particularly limited, and is preferably 0.1 to 50 μm. The volume average particle size of the positive electrode active material particles can be measured in the same manner as the volume average particle size of the negative electrode active material described above.
[0372] The positive electrode active material obtained by the calcination method may be cleaned with at least one cleaning agent selected from the group consisting of water, an acidic aqueous solution, an alkaline aqueous solution, and an organic solvent before use.
[0373] The positive electrode active material is similar to the negative electrode active material, and at least a portion of its surface can be coated with the above-mentioned surface covering agent, a coating layer containing sulfur or phosphorus, and / or a surface coating using active light or active gas can also be implemented. Among them, the mode in which at least a portion of the surface of the positive electrode active material is coated with a coating layer containing a specific solid electrolyte is one of the preferred modes of the positive electrode active material.
[0374] The thickness of the coating layer containing the solid electrolyte possessed by the positive electrode active material is not particularly limited, and is, for example, 5 nm to 10 μm.
[0375] The method for forming a coating layer on the surface of the positive electrode active material is not particularly limited, and it can be applied to a method of coating the surface of the positive electrode active material with a coating layer by spraying a solution containing a surface covering agent and performing a drying process, and a method of evaporating a coating layer on the surface of the positive electrode active material by sputtering, etc., and other known methods. Regarding the method of forming a coating layer on the surface of the positive electrode active material, reference can also be made to the methods described in Japanese Patent Publication No. 2017-059393 and Japanese Patent Publication No. 2015-056307, and these records are incorporated into this specification.
[0376] The positive electrode active material may be used alone or in combination of two or more.
[0377] (Other ingredients)
[0378] The active material layer-forming composition may contain other components in addition to the specific solid electrolyte and the active material.
[0379] The active material layer-forming composition may contain a conductive auxiliary agent.
[0380] As the conductive aid, a substance known as a conductive aid can be used. As the conductive aid, for example, graphites such as natural graphite and artificial graphite, carbon blacks such as acetylene black, Ketjen black and furnace black, amorphous carbons such as needle coke, fibrous carbons such as vapor-grown carbon fibers and carbon nanotubes, and carbonaceous materials such as graphene and fullerene can be cited as electronic conductive materials. In addition, conductive polymers such as polyaniline, polypyrrole, polythiophene, polyacetylene and polyphenylene derivatives can be used.
[0381] Furthermore, a conductive auxiliary agent that does not contain carbon atoms, such as metal powder or metal fiber, may be used.
[0382] In addition, the conductive aid refers to a component that does not insert and release Li ions during battery charging and discharging and does not function as an active material. Therefore, among the conductive aids, substances that function as active materials in the active material layer during battery charging and discharging are also classified as active materials rather than conductive aids. During battery charging and discharging, whether or not it functions as an active material cannot be determined uniquely, but can be determined by the combination with the active material.
[0383] Furthermore, other components include the above-mentioned binder and lithium salt.
[0384] The active material layer-forming composition may contain a dispersion medium. The types and preferred embodiments of the dispersion medium are the same as the types and preferred embodiments of the dispersion medium that may be contained in the above-mentioned solid electrolyte layer-forming composition.
[0385] The composition for forming an active material layer may contain, as components other than the above-mentioned components, ionic liquids, thickeners, cross-linking agents (substances that undergo cross-linking reactions by free radical polymerization, condensation polymerization or ring-opening polymerization), polymerization initiators (substances that generate acids or free radicals by heat or light, etc.), defoaming agents, leveling agents, dehydrating agents and / or antioxidants.
[0386] The method for forming the active material layer using the active material layer-forming composition is not particularly limited, and an example thereof includes a method in which a coating film formed by applying the active material layer-forming composition to a current collector described later is subjected to a pressure treatment.
[0387] The coating method of the active material layer-forming composition is not particularly limited, and examples thereof include spray coating, spin coating, dip coating, slit coating, spray coating, aerosol deposition, thermal spraying, and bar coating.
[0388] In addition, after applying the active material layer-forming composition, the obtained coating film may be dried as needed. The drying treatment is preferably performed before the above-mentioned pressurization treatment. The drying temperature is not particularly limited, but as a lower limit, it is preferably 30°C or more, more preferably 60°C or more, and further preferably 80°C or more. As an upper limit of the drying temperature, it is preferably 300°C or less, and more preferably 250°C or less.
[0389] The method of pressurizing the coating film of the active material layer-forming composition is not particularly limited, and examples thereof include a method using a known pressurizing device (for example, a hydraulic cylinder press).
[0390] The pressure applied during the pressurization treatment is not particularly limited, but is preferably 5 to 1500 MPa, more preferably 300 to 600 MPa.
[0391] The time for the pressure treatment is not particularly limited, but is preferably 1 minute to 6 hours, more preferably 1 to 20 minutes, from the viewpoint of productivity.
[0392] Furthermore, during the pressure treatment, a heat treatment may be performed. The heating temperature during the heat treatment is not particularly limited, but is preferably 30 to 300° C., and the heating time is preferably 1 minute to 6 hours.
[0393] The atmosphere during the pressurization process is not particularly limited, and examples thereof include atmospheric air, dry air (dew point -20°C or lower), and an inert gas (for example, argon, helium, and nitrogen) atmosphere.
[0394] (Active material layer)
[0395] One preferred embodiment of the active material layer is an active material layer formed using the active material layer-forming composition and containing a specific solid electrolyte. Among them, a positive electrode active material layer containing a specific solid electrolyte and a positive electrode active material is preferred.
[0396] The content of the specific solid electrolyte in the active material layer is not particularly limited, but is preferably 10 to 70% by mass, more preferably 20 to 50% by mass, based on the total mass of the active material layer.
[0397] The content of the active material (positive electrode active material or negative electrode active material) in the active material layer is not particularly limited, but is preferably 30 to 90 mass %, more preferably 50 to 80 mass %, based on the total mass of the active material layer.
[0398] The active material layer may contain other components in addition to the active material and the specific solid electrolyte. Examples of the other components include components that may be contained in the active material layer-forming composition excluding the dispersion medium.
[0399] <Electrode Sheet for All-Solid State Secondary Batteries>
[0400] A specific solid electrolyte can be used to form an electrode sheet for an all-solid-state secondary battery.
[0401] An electrode sheet for an all-solid-state secondary battery (hereinafter also referred to simply as an "electrode sheet") is a sheet-shaped molded body that can form an electrode active material layer of an all-solid-state secondary battery, and can be preferably used as an electrode or a laminate of an electrode and a solid electrolyte layer.
[0402] The electrode sheet has at least an active material layer. The specific solid oxide is preferably contained in at least one layer of the active material layer of the electrode sheet.
[0403] The electrode sheet may be a laminate formed by forming an active material layer on a substrate (collector), or may be formed by only an active material layer monomer without a substrate. In addition, as an electrode sheet, it also includes a method in which a collector, an active material layer and a solid electrolyte layer are stacked in sequence, and a method in which a collector, an active material layer, a solid electrolyte layer and an active material layer are stacked in sequence. The electrode sheet may have other layers besides the active material layer, the collector and the solid electrolyte layer.
[0404] The thickness of each layer constituting the electrode sheet is the same as the thickness of each layer described in the all-solid-state secondary battery to be described later.
[0405] The method for producing the electrode sheet is not particularly limited, and the electrode sheet can be produced, for example, by forming an active material layer using the above-mentioned active material layer-forming composition.
[0406] For example, there is a method in which the composition for forming an active material layer is applied directly on the current collector or via another layer to form a coating film, and the obtained coating film is subjected to a pressure treatment.
[0407] As a method of applying the composition for forming an active material layer and a method of subjecting the coating film to a pressure treatment, the methods described in the section on the composition for forming an active material layer can be cited.
[0408] [Binder (Third Embodiment)]
[0409] As a third embodiment of the present invention, the following adhesives can be mentioned.
[0410] The binder according to the present embodiment is represented by the following general formula (I).
[0411] A a B b O c X d (I)
[0412] In the general formula (I), A represents at least one selected from Li and Na.
[0413] X represents at least one selected from F, Cl, Br, I, S, N, H, Se, Te, C, P, Si, Al, Ga, In, Ge, As, Sh and Sn.
[0414] a represents the number of moles of each element represented by A, and is 1.75<a<2.45.
[0415] b is 3.75<b<4.25.
[0416] c is 6.50<c<10.00.
[0417] d represents the total number of moles of the element represented by X, and is 0<d<0.50.
[0418] The present inventors have found that a compound containing predetermined amounts of elements A, B and O and a predetermined amount of element X has excellent ion conductivity and excellent adhesion (adhesion) to other components and is therefore particularly useful as a binder for secondary batteries.
[0419] The element composition and physical properties of the binder of the present embodiment, including preferred aspects thereof, are the same as those of the first specific solid electrolyte described above.
[0420] [Binder (Fourth Embodiment)]
[0421] As a fourth embodiment of the present invention, the following adhesives can be mentioned.
[0422] The binder of the present embodiment contains Li, B, O, and X, and satisfies the following requirements A-1 and A-2.
[0423] X represents at least one element selected from F, Cl, Br, I, S, N, H, Se, Te, C, P, Si, Al, Ga, In, Ge, As, Sb and Sn.
[0424] Requirement A-1: In the reduced two-body distribution function G(r) obtained from the X-ray total scattering measurement of the oxide solid electrolyte, there is a peak located at r The first peak and the top peak in the range of r are The second peak in the range of , the G (r) of the peak of the first peak and the G (r) of the peak of the second peak are greater than 1.0, and when r is greater than And for The absolute value of G(r) in the following range is less than 1.0.
[0425] The present inventors have found that a compound containing element X in addition to Li, B and O and satisfying the above requirements A-1 and A-2 has excellent ion conductivity and excellent adhesion to other components, and is therefore particularly useful as a binder for secondary batteries.
[0426] As described for specific solid electrolytes, since the binder of the present embodiment that satisfies requirements A-1 and A-2 exhibits elastic properties that allow for easy plastic deformation, it can be inferred that the molded body formed by pressurizing the binder, etc., has excellent adhesion to other ion conductors, low interface resistance, and excellent ion conductivity.
[0427] The element composition and physical properties of the binder of the present embodiment, including preferred aspects thereof, are the same as those of the second specific solid electrolyte described above.
[0428] Hereinafter, unless otherwise specified, the adhesive agent of the third embodiment and the adhesive agent of the fourth embodiment are not distinguished and are described together. Furthermore, the adhesive agent of the third embodiment and the adhesive agent of the fourth embodiment are also collectively referred to as a "specific adhesive agent".
[0429] The method for producing the specific binder, including preferred aspects thereof, is the same as the method for producing the specific solid electrolyte described above.
[0430] [Molded article of specific adhesive]
[0431] The molded body of the specific binder (hereinafter also referred to as “second specific molded body”) is formed using the above-mentioned specific binder.
[0432] The method for forming the second specific molded body is not particularly limited, and for example, a method of forming the molded body by subjecting the specific binder to a pressure treatment may be mentioned. That is, the second specific molded body is preferably formed by subjecting the specific binder to a pressure treatment (pressure molding process).
[0433] The method of the press treatment is the same as the method of the press treatment already described as the method of forming the specific molded body.
[0434] The second specific compact may be a composite body including a specific binder and other components other than the specific binder. Other components included in the second specific compact include, for example, a specific solid electrolyte, a second lithium compound, and other binders other than the specific binder.
[0435] In order to further improve the ion conductivity, the second specific molded body preferably contains at least one selected from the group consisting of a specific solid electrolyte and a second lithium compound. The specific solid electrolyte and the second lithium compound are as described above including preferred embodiments thereof.
[0436] Examples of another binder contained in the second specific molded body in addition to the specific binder include the above-mentioned organic high molecular compound (polymer) contained as a binder in the above-mentioned specific molded body.
[0437] When the second specific molded body contains other binders, the content of the other binders is preferably 0.1 to 3% by mass, more preferably 0.5 to 1% by mass, based on the total mass of the second specific molded body.
[0438] The second specific compact may contain a lithium compound other than the second lithium compound and / or a solid electrolyte other than the specific solid electrolyte.
[0439] The ion conductivity of the second specific molded body is not particularly limited, but is preferably 1.0×10 -6 S / cm or more, more preferably 1.0×10 -5 The method for measuring the ion conductivity of the second specific molded body is the same as the method for measuring the ion conductivity of the specific binder.
[0440] 〔use〕
[0441] The above-mentioned specific adhesive can be used for various purposes.
[0442] For example, it can be used in various batteries (for example, all-solid secondary batteries, solid oxide fuel cells, batteries using solid oxide vapor electrolysis, and semi-solid secondary batteries and lithium ion secondary batteries using liquid electrolytes). Among them, the specific binder is preferably used in all-solid secondary batteries.
[0443] More specifically, the specific binder is preferably used as a binder contained in any one of a solid electrolyte layer, a positive electrode active material layer, and a negative electrode active material layer in an all-solid-state secondary battery.
[0444] <Solid Electrolyte Layer>
[0445] Preferred applications of the specific binder include a solid electrolyte layer containing at least the specific binder and a solid electrolyte.
[0446] The content of the specific binder in the solid electrolyte layer is not particularly limited, but is preferably 3 to 50% by mass, more preferably 5 to 30% by mass, based on the total mass of the solid electrolyte layer.
[0447] As the solid electrolyte contained in the solid electrolyte layer, a specific solid electrolyte and other solid electrolytes other than the specific solid electrolyte can be cited. The content of the solid electrolyte in the solid electrolyte layer is preferably 50% by mass or more, and more preferably 80% by mass or more relative to the total mass of the solid electrolyte layer. The upper limit is not particularly limited and can be the remainder of the specific binder.
[0448] The method for forming the solid electrolyte layer is not particularly limited, and an example thereof includes a method of applying a coating film formed by applying a solid electrolyte layer-forming composition containing a specific binder and a solid electrolyte and subjecting it to a pressure treatment.
[0449] The solid electrolyte layer-forming composition may contain a dispersion medium, or may contain a specific binder, a solid electrolyte, and other components other than the dispersion medium.
[0450] Regarding the specific method for forming a solid electrolyte layer and the composition for forming a solid electrolyte layer, including preferred embodiments thereof, reference can be made to the contents already described as specific examples of uses of the specific solid electrolyte.
[0451] <Active material layer>
[0452] Another preferred application of the specific binder is an active material layer containing at least the specific binder and an active material.
[0453] Regarding the structure and manufacturing method of the active material layer containing at least a specific binder and an active material, the specific binder is used instead of the specific solid electrolyte. Other than that, including its preferred embodiment, reference can be made to the contents described for the active material layer containing a specific solid electrolyte.
[0454] <Electrode sheet>
[0455] Another preferred application of the specific binder is an electrode sheet formed using the specific binder.
[0456] Regarding the structure and manufacturing method of the electrode sheet formed using a specific adhesive, a specific adhesive is used instead of a specific solid electrolyte. In addition, including its preferred embodiment, reference can be made to the contents already described for the electrode sheet for an all-solid-state secondary battery formed by using a specific solid electrolyte.
[0457] [All-solid-state secondary battery]
[0458] The all-solid-state secondary battery has a positive electrode for the all-solid-state secondary battery (hereinafter referred to as the "positive electrode"), a negative electrode for the all-solid-state secondary battery (hereinafter referred to as the "negative electrode") facing the positive electrode, and a solid electrolyte layer arranged between the positive electrode and the negative electrode.
[0459] In the all-solid-state secondary battery, at least one layer selected from the positive electrode, the negative electrode, and the solid electrolyte layer contains at least one selected from a specific solid electrolyte and a specific binder.
[0460] In an all-solid-state secondary battery, it is preferred that at least one of the positive electrode and the negative electrode comprises at least one selected from a specific solid electrolyte and a specific binder, or the solid electrolyte layer comprises a specific solid electrolyte. Among them, it is more preferred that at least one of the positive electrode active material layer (or positive electrode) and the solid electrolyte layer comprises a specific solid electrolyte, and it is further preferred that the solid electrolyte layer comprises a specific solid electrolyte.
[0461] Hereinafter, the positive electrode and the negative electrode are also collectively referred to as "electrode".
[0462] The electrode has an active material layer, preferably a current collector (positive electrode current collector or negative electrode current collector) and an active material layer formed on the current collector. As described above, the active material layer is a layer having an active material, and may further have a solid electrolyte. The active material layer preferably has at least a specific solid electrolyte or a specific binder.
[0463] That is, the electrode preferably has an active material layer containing an active material and a specific solid electrolyte or a specific binder, and a current collector.
[0464] Among them, in the all-solid-state secondary battery, it is preferred that the positive electrode active material layer has a specific solid electrolyte. That is, the positive electrode preferably has a positive electrode active material layer containing a positive electrode active material and a specific solid electrolyte, and a positive electrode current collector.
[0465] Below, reference Figure 8 , an example of an embodiment of the all-solid-state secondary battery is described. The all-solid-state secondary battery of the present invention is not limited to Figure 8 The method shown in .
[0466] Figure 8It is a cross-sectional view showing an example of the structure of the all-solid-state secondary battery of the present invention. Figure 8 The all-solid-state secondary battery 10 shown in FIG. 1 has a laminated body, which is formed by laminating a negative electrode collector 1, a negative electrode active material layer 2, a solid electrolyte layer 3, a positive electrode active material layer 4, and a positive electrode collector 5 in order from the negative electrode side. In the all-solid-state secondary battery 10, at least one layer selected from the solid electrolyte layer 3, the positive electrode active material layer 4, and the negative electrode active material layer 2 contains a specific solid electrolyte. Preferably, at least one layer of the solid electrolyte layer 3 and the positive electrode active material layer 4 contains a specific solid electrolyte.
[0467] exist Figure 8 In the all-solid secondary battery 10 shown in FIG. 1 , each layer is in contact with each other and has an adjacent structure. By adopting this structure, electrons (e) are supplied to the negative electrode side during charging. - ), in which lithium ions (Li + ) are accumulated. On the other hand, during discharge, the lithium ions (Li + ) returns to the positive electrode side, and supplies electrons to the working portion 6. In the example shown in the figure, a light bulb is used as the working portion 6 in a simulated manner, and a structure is constructed to light the light bulb by discharge.
[0468] The solid electrolyte layer 3 is disposed between the positive electrode and the negative electrode and contains a solid electrolyte. The solid electrolyte layer 3 preferably contains a specific solid electrolyte. The solid electrolyte layer containing the specific solid electrolyte is as described above.
[0469] When the solid electrolyte layer 3 does not contain a specific solid electrolyte, the solid electrolyte constituting the solid electrolyte 3 is not particularly limited, and examples thereof include oxide solid electrolytes other than sulfide solid electrolytes and specific solid electrolytes.
[0470] The thickness of the solid electrolyte layer 3 is not particularly limited, but is preferably 10 to 1000 μm, more preferably 20 μm or more and less than 500 μm, in consideration of the size of the all-solid-state secondary battery.
[0471] The positive electrode active material layer 4 contains the above-mentioned positive electrode active material, and may contain a specific solid electrolyte. The positive electrode active material layer containing the specific solid electrolyte is as described above.
[0472] Furthermore, as the positive electrode active material layer 4 not containing a specific solid electrolyte, in the positive electrode active material layer containing the above-mentioned specific solid electrolyte, a method of replacing the specific solid electrolyte with at least one selected from a sulfide solid electrolyte and an oxide solid electrolyte other than the specific solid electrolyte can be cited.
[0473] The thickness of the positive electrode active material layer is not particularly limited, but is preferably 10 to 1000 μm, more preferably 20 μm or more and less than 500 μm, and further preferably 50 μm or more and less than 500 μm, in consideration of the size of the all-solid-state secondary battery.
[0474] The negative electrode active material layer 2 contains the above-mentioned negative electrode active material, and may contain a specific solid electrolyte. The components contained in the negative electrode active material layer 2 and the method for producing the negative electrode active material layer 2 are as described above.
[0475] As the negative electrode active material layer 2 not containing the specific solid electrolyte, the negative electrode active material layer containing the above-mentioned specific solid electrolyte may contain at least one selected from a sulfide solid electrolyte and an oxide solid electrolyte other than the specific solid electrolyte instead of the specific solid electrolyte.
[0476] The thickness of the negative electrode active material layer 2 is not particularly limited, but is preferably 10 to 1000 μm, more preferably 20 μm or more and less than 500 μm, and further preferably 50 μm or more and less than 500 μm, in consideration of the size of the all-solid-state secondary battery.
[0477] Furthermore, the thickness of at least one of the positive electrode active material layer and the negative electrode active material layer is preferably 50 μm or more and less than 500 μm.
[0478] 〔Current Collector〕
[0479] As the positive electrode current collector 5 and the negative electrode current collector 1, electron conductors are preferred.
[0480] As the material forming the positive electrode current collector, aluminum, aluminum alloy, stainless steel, nickel and titanium can be cited, preferably aluminum or aluminum alloy. As the positive electrode current collector, a current collector having a thin film formed by treating the surface of aluminum or stainless steel with carbon, nickel, titanium or silver can also be cited.
[0481] As the material forming the negative electrode current collector, aluminum, copper, copper alloy, stainless steel, nickel and titanium can be enumerated, preferably aluminum, copper, copper alloy or stainless steel. In addition, as the negative electrode current collector, a current collector having a film formed by processing with carbon, nickel, titanium or silver on the surface of aluminum, copper, copper alloy or stainless steel can also be enumerated.
[0482] The current collector is usually in the form of a thin film sheet, but may also be in other shapes.
[0483] The thickness of the current collector is not particularly limited, but is preferably 1 to 500 μm.
[0484] Furthermore, it is preferred that the surface of the current collector be provided with irregularities by surface treatment depending on the application.
[0485] The all-solid-state secondary battery can be used in the state of the laminate having the above structure according to the application, but it is preferable to further encapsulate the laminate having the above structure in a frame in order to provide a dry cell form.
[0486] The frame may be a metal frame or a resin (plastic) frame.
[0487] As the metal frame, for example, an aluminum alloy frame and a stainless steel frame can be cited. The metal frame includes a positive electrode side frame and a negative electrode side frame that are not electrically connected to each other, and preferably has a structure in which the positive electrode side frame is electrically connected to the positive electrode collector and the negative electrode side frame is electrically connected to the negative electrode collector. In this case, the positive electrode side frame and the negative electrode side frame are preferably joined via a short circuit prevention gasket to be integrated.
[0488] The all-solid-state secondary battery of the present invention is not limited to the above-mentioned specific structure, and may have a structure other than the above-mentioned structure.
[0489] For example, in the above-mentioned all-solid-state secondary battery 10, at least one layer selected from the solid electrolyte layer 3, the positive electrode active material layer 4 and the negative electrode active material layer 2 contains a specific solid electrolyte, but the all-solid-state secondary battery of the present invention may be an all-solid-state secondary battery in which at least one layer selected from the solid electrolyte layer, the positive electrode active material layer and the negative electrode active material layer contains a specific adhesive.
[0490] [Method for manufacturing all-solid-state secondary battery]
[0491] The method for producing the above-mentioned all-solid-state secondary battery is not particularly limited, and known methods may be mentioned. Among them, the method using the above-mentioned active material layer-forming composition and / or solid electrolyte layer-forming composition is preferred.
[0492] As a method for manufacturing an all-solid-state secondary battery, for example, the following method can be cited: a first step of forming a coating film containing a positive electrode active material by applying a positive electrode active material layer forming composition on a metal foil as a positive electrode collector; a second step of forming a coating film containing a solid electrolyte by applying a solid electrolyte layer forming composition on the coating film formed in the first step; a third step of forming a coating film containing a negative electrode active material by applying a negative electrode active material layer forming composition on the coating film formed in the second step; a fourth step of overlapping a negative electrode collector (metal foil) on the coating film formed in the third step; and a fifth step of applying a pressure treatment to the obtained laminate to produce an all-solid-state secondary battery having a structure in which a positive electrode collector, a positive electrode active material layer, a solid electrolyte layer, a negative electrode active material layer, and a negative electrode collector are sequentially laminated. The laminate produced by the above method can be encapsulated in a frame to produce an all-solid-state secondary battery having a frame.
[0493] Furthermore, the order of forming each layer can be reversed to sequentially form a coating containing a negative electrode active material, a coating containing a solid electrolyte, and a coating containing a positive electrode active material on the negative electrode collector, and after further overlapping the positive electrode collector, the obtained stack can be pressurized to manufacture an all-solid-state secondary battery.
[0494] As another method, a positive electrode active material layer, a solid electrolyte layer, and a negative electrode active material layer may be separately prepared and then stacked to produce an all-solid-state secondary battery.
[0495] The all-solid-state secondary battery is preferably initialized after manufacture or before use. The method of initialization is not particularly limited, and for example, it can be performed by performing initial charge and discharge under increased pressure, and then releasing the pressure until the pressure condition range when the all-solid-state secondary battery is used is reached.
[0496] [Application of all-solid-state secondary batteries]
[0497] All-solid-state secondary batteries can be applied to various purposes. There is no particular limitation on the application mode. For example, as the purpose when being carried on electronic equipment, notebook computers, pen input computers, mobile computers, e-book readers, mobile phones, wireless telephone handsets, pagers, handheld terminals, portable fax transceivers, portable copiers, portable printers, stereo headphones, video movie players, LCD TVs, handheld cleaners, portable CD players, mini-disc players, electric shavers, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios and backup power supplies can be cited. As other consumer products, automobiles, electric cars, motors, lighting equipment, toys, game consoles, load regulators, clocks, flashlights, cameras and medical equipment (pacemakers, hearing aids and shoulder massagers, etc.) can be cited. In addition, it can be used as various military supplies and the universe. And, it can also be combined with solar cells.
[0498] Example
[0499] Hereinafter, the present invention will be described in further detail based on Examples, but the present invention is not limited thereto. In the following Examples, "parts" and "%" indicating the composition are based on mass unless otherwise specified.
[0500] [Example 1]
[0501] <Preparation of specific solid electrolyte>
[0502] Using a ball mill (P-7 manufactured by FRITSCH), under the conditions of pot: YSZ (45 ml), grinding balls: YSZ (average particle size: 5 mm, number: 50), rotation speed: 370 rpm (revolutions per minute), LBO powder amount: 1 g, atmosphere: air, ball mill processing time: 100 hours, powdered Li2B4O7 crystals (LBO powder) (manufactured by RAREMETALL[C Co., Ltd.) were ball-milled to obtain micronized lithium tetraborate (hereinafter also referred to as "LBO micronized material").
[0503] To the obtained LBO fine material, 0.02 g (2 mass % for LBO powder) of LiFSI (Li(FSO2)2N) was added as a specific element source for doping F, S and N, and the mixture was further ground for 100 hours to obtain a powdery specific solid electrolyte (composite oxide 1).
[0504] The elemental analysis of the obtained composite oxide 1 revealed that the composition of the composite oxide 1 was Li 1.98 B4O 6.83 F 0.08 S 0.07 N 0.04 In addition, among the elements contained in the composite oxide 1, elemental analysis was performed for Li and B by ICP-OES, for F and S by combustion ion chromatography, and for N by inert gas fusion method. For O, the analyzed masses of the elements other than O were added and calculated as the difference from the total amount of the powder.
[0505] <Production and Evaluation of Specific Solid Electrolyte Molded Body>
[0506] The powdered composite oxide 1 obtained above was pressed at 27°C (room temperature) and an effective pressure of 220 MPa to obtain a molded body of a specific solid electrolyte (powder pressed body 1). The ion conductivity of the obtained powder pressed body 1 was measured, and the ion conductivity of the powder pressed body 1 at 27°C was 2.8×10 -7 S / cm, at 60°C: 1.6×10 -6 S / cm.
[0507] The ionic conductivity of the solid electrolyte was calculated by configuring electrodes consisting of two In foils to sandwich the produced solid electrolyte molded body, measuring the AC impedance between the two In electrodes in the measurement frequency range of 1 Hz to 1 MHz under the conditions of a measurement temperature of 27°C and an applied voltage of 100 mV, and analyzing the arc diameter of the obtained Cole-Cole plot.
[0508] The particle size distribution of the composite oxide 1 obtained above was about several hundred nm to 10 μm, the average particle size was 1.6 μm, and the median particle size (D50) was 1.5 μm.
[0509] The particle size distribution of the specific solid electrolyte prepared in each example was calculated by obtaining particle images using a flow particle image analysis method to prepare a histogram (particle size distribution) of the particle size of the specific solid electrolyte. The above particle size corresponds to the equivalent circle diameter.
[0510] The bulk elastic modulus of the composite oxide 1 obtained in the above was 36 GPa. The bulk elastic modulus of the LBO powder before the ball milling treatment was 47 GPa.
[0511] The determination of the bulk modulus of the specific solid electrolyte produced in each embodiment is implemented by ultrasonic attenuation method. Specifically, first, a suspension obtained by suspending a specific solid electrolyte in pure water is produced. The content of the specific solid electrolyte in the suspension is set to 1.2% by mass relative to the total mass of the suspension. Then, the ultrasonic attenuation spectrum of the above suspension is measured, and the bulk modulus (GPa) of the specific solid electrolyte is obtained by fitting based on the scattering attenuation theory formula. In addition, when calculating the bulk modulus, the density of the specific solid electrolyte is set to 2.3g / mL, and the Poisson's ratio is fitted as 0.12. In addition, regarding the fitting based on the above scattering attenuation theory formula, the bulk modulus is calculated using the formulas (7), (12) and (13) recorded in Kohjiro Kubo et al., Ultrasonics 62 (2015) 186-194 pages.
[0512] Using composite oxide 1, SPring-8 BL04B2 (accelerating voltage: 61.4 keV, wavelength: ) were used for X-ray total scattering measurement. The sample was sealed in a 2 mm φ or 1 mm φ KAPTON capillary and the experiment was performed under vacuum. In addition, as described above, the obtained data were Fourier transformed to obtain the reduced two-body distribution function G(r). Figure 1 The reduced two-body distribution function G(r) obtained from the composite oxide 1 is shown in FIG.
[0513] The results of the analysis show that in the reduced two-body distribution function G(r) obtained from the X-ray total scattering measurement, when r is In the range of , the peak G(r) is greater than 1.0, and the peak is located at The G(r) of the first peak and the top peak of the The second peak of the reduced two-body distribution function G(r) was confirmed when r was greater than And for The absolute value of G(r) in the following range is less than 1.0. From the above, it was confirmed that the composite oxide 1 as the molded body of the specific solid electrolyte obtained in the above-mentioned method satisfies both the requirements 1-1 and 1-2 (reference Figure 1 In particular, from the comparison with Comparative Example 1 described later, it was confirmed that in the presence of a specific element source, in the composite oxide 1 of Example 1 manufactured by the manufacturing method having a step of mechanically grinding the lithium tetraborate compound, the peak of G(r) becomes lower in the range where r is greater than 5 Å and less than 10 Å.
[0514] The above results confirm that there is almost no long-range order in Composite Oxide 1, and Composite Oxide 1 is amorphous. On the other hand, the peaks attributable to the BO distance and BB distance observed in general lithium tetraborate crystals are maintained in Composite Oxide 1. It is inferred that since general lithium tetraborate crystals have a structure (diborate structure) in which BO4 tetrahedrons and BO3 triangles exist in a 1:1 ratio, this structure is maintained in Composite Oxide 1.
[0515] The composite oxide 1 was subjected to solidification at 20°C and 120°C. 7 In the Li-NMR measurement, the full width at half maximum (FWHM 1) of the peak whose chemical shift appears in the range of -100 to +100 ppm in the spectrum obtained in the measurement at 20° C. and the full width at half maximum (FWHM 2) of the peak whose chemical shift appears in the range of -100 to +100 ppm in the spectrum obtained in the measurement at 120° C. were obtained. From the obtained FWHM 1 and FWHM 2, the percentage of the ratio of FWHM 2 to FWHM 1 {(FWHM 2 / FWHM 1)×100}, i.e., the FWHM ratio (%) of the composite oxide 1 was calculated to be 65%.
[0516] Raman imaging was performed on the powder compact 1. The measurement conditions were as follows: excitation light of 532 nm, objective lens of 100 times, point scanning in mapping mode, 1 μm pitch, exposure time of 1 second per point, accumulation and integration times of 1 time, and measurement range of 70 μm×50 μm. Noise was removed from the obtained data by PCA processing.
[0517] In the Raman spectrum obtained in this way, the 600-850 cm -1 The coefficient of determination was obtained by linear regression analysis based on the least square method in the wave number region. The coefficient of determination of the obtained powder compact 1 was 0.9952.
[0518] [Example 2]
[0519] In the LBO fine material prepared in Example 1, as a specific element source for doping F, S and N, in addition to adding 0.05 g (5 mass % for LBO powder) of LiFSI [Li (FSO2) 2N], a powdered specific solid electrolyte (composite oxide 2) was prepared according to the method described in Example 1. The elemental analysis results showed that the composition of the obtained composite oxide 2 was Li 2.01 B4O 7.47 F 0.12 S 0.12 N 0.07 .
[0520] Next, the powdered composite oxide 2 obtained in the above was pressed at 27°C (room temperature) and an effective pressure of 220 MPa to obtain a compact of a specific solid electrolyte (compressed powder 2). The ion conductivity of the obtained compressed powder 2 at 27°C was 3.0×10 -7 S / cm, at 60°C: 1.7×10 -6 S / cm.
[0521] [Example 3]
[0522] In the LBO fine material prepared in Example 1, as a specific element source for doping I, 0.05 g (5 mass % for LBO powder) of LiI was added, and a powdered specific solid electrolyte (composite oxide 3) was prepared according to the method described in Example 1. The elemental analysis results showed that the composition of the obtained composite oxide 3 was Li 2.05 B4O 9.28 I 0.07 In addition, elemental analysis of iodine was performed by burning IC.
[0523] Next, the powdered composite oxide 3 obtained in the above was pressed at 27°C (room temperature) and an effective pressure of 220 MPa to obtain a compact (powder compact 3) of a specific solid electrolyte. The ion conductivity of the obtained powder compact 3 at 27°C was 3.1×10 -5 S / cm, at 60°C: 9.4×10 -5 S / cm.
[0524] [Example 4]
[0525] In the LBO fine material prepared in Example 1, as a specific element source for doping Cl, 0.02 g (2 mass % for LBO powder) of LiCl was added, and a powdered specific solid electrolyte (composite oxide 4) was prepared according to the method described in Example 1. The elemental analysis results showed that the composition of the obtained composite oxide 4 was Li 2.03 B4O9.80 Cl 0.06 In addition, elemental analysis of chlorine was performed by burning IC.
[0526] Next, the powdered composite oxide 4 obtained in the above was pressed at 27°C (room temperature) and an effective pressure of 220 MPa to obtain a compact of a specific solid electrolyte (compressed powder 4). The ion conductivity of the obtained compressed powder 4 at 27°C was 2.3×10 -5 S / cm, 3.6×10 at 60°C -5 S / cm.
[0527] [Comparative Example 1]
[0528] The LBO powder used in Comparative Example 1 was subjected to elemental analysis, and the composition of the obtained LBO powder was Li 1.96 B 4.00 O 6.80 The LBO powder was compacted at 27° C. (room temperature) and an effective pressure of 220 MPa to obtain a comparative compact C1. The ion conductivity of the obtained compact C1 could not be detected as described later.
[0529] Furthermore, according to the method described in Example 1, total X-ray scattering measurement was performed using LBO powder to obtain the reduced two-body distribution function G(r). Fig. 9 The reduced two-body distribution function G(r) obtained from LBO powder is shown in FIG.
[0530] The analysis results show that the reduced two-body distribution function G(r) obtained from the X-ray total scattering measurement of LBO powder has a peak located at The first peak (corresponding to the vicinity of BO) and the top peak are located at The second peak (corresponding to the vicinity of BB), the G(r) of the top of the first and second peaks is greater than 1.0 (reference Fig. 9 ). And, in addition, there is a peak located at and The absolute value of G(r) at the top of each peak is greater than 1.0 (reference Fig. 9 ).
[0531] [Reference Example 1]
[0532] The elemental analysis of the LBO fine material prepared in Example 1 showed that the composition of the LBO fine material was Li 1.94 B4O 680 .
[0533] Next, the LBO fine material was pressed at 27°C (room temperature) and an effective pressure of 220 MPa to obtain a reference powder compact (powder compact R1). The ion conductivity of the obtained powder compact R1 at 27°C was 7.5×10 -9 S / cm, 7.5×10 at 60°C -8 S / cm.
[0534] The particle size distribution of each composite oxide (or LBO fine product) obtained in Examples 2 to 4 and Reference Example 1 was about several hundred nm to 10 μm, the average particle size was 1.6 μm, and the median particle size (D50) was 1.5 μm.
[0535] Furthermore, according to the method described in Example 1, the bulk elastic modulus, the reduced two-body distribution function G(r), and the ratio of the half-maximum full width 2 to the half-maximum full width 1 were obtained for the composite oxides 2 to 4 obtained in Examples 2 to 4, the LBO powder obtained in Comparative Example 1, and the LBO fine material used in Reference Example 1. Furthermore, according to the method described in Example 1, the coefficient of determination was obtained for each of the pressed powders obtained in Examples 2 to 4, Comparative Example 1, and Reference Example 1. The evaluation results based on the respective measurements are collectively shown in Table 2.
[0536] In Table 2, the column “Ion conductivity (S / cm)” indicates a numerical value without exponents. For example, “2.8E-07” indicates “2.8×10 -7 ”.
[0537] In Table 2, the column "Bulk elastic modulus (GPa)" shows the measured value (unit: GPa) of each composite oxide, LBO fine material or LBO powder measured by the above-mentioned method based on the ultrasonic attenuation method.
[0538] In the column "Requirement 1-1" in Table 2, there is a peak at r in the reduced two-body distribution function G(r) obtained from each composite oxide, LBO fine material or LBO powder. The first peak and the top peak in the range of r are In the case where the G(r) of the top of the first peak and the G(r) of the top of the second peak are greater than 1.0, the condition 1 is recorded as "A", and the condition 1 is not satisfied, the condition is recorded as "B". In the column of "Condition 1-2", in the case where the reduced two-body distribution function G(r) obtained from each composite oxide, LBO fine material or LBO powder is satisfied, the condition 1-2 is recorded as "A". And for In the case of requirement 1-2 where the absolute value of G(r) is less than 1.0 within the following range, it is described as "A", and in the case where the above requirement 1-1 is not satisfied, it is described as "B".
[0539] In Table 2, the column "Full Width at Half Maximum Ratio (%)" indicates the solid state of each composite oxide, LBO fine material or LBO powder at 20°C and 120°C. 7 The ratio of the full width at half maximum 2 to the full width at half maximum 1 respectively obtained by Li-NMR measurement is {(full width at half maximum 2 / full width at half maximum 1)×100} (%).
[0540] In Table 2, the “Determination Coefficient” column shows that in the Raman spectrum of each powder compact, the -1 The coefficient of determination was obtained by linear regression analysis based on the least squares method within the wavenumber region.
[0541] [Table 1]
[0542]
[0543] [Table 2]
[0544]
[0545] As described above, it was confirmed that the oxide solid electrolyte of the present invention has superior ion conductivity compared to the LBO powder of Comparative Example 1.
[0546] (X-ray diffraction measurement)
[0547] X-ray diffraction measurement was performed using CuKα rays on the powdery specific solid electrolyte (complex oxide 2) prepared in Example 2 and the LBO powder used in Comparative Example 1. The measurement conditions were 0.01° / pitch and 3° / min.
[0548] Fig.11 The X-ray diffraction pattern of the LBO powder of Comparative Example 1 is shown in FIG. Fig.11 As shown, the LBO powder used in Comparative Example 1 does not meet the above-mentioned requirement 3, and multiple peaks with small widths are observed. More specifically, the strongest peak corresponding to the (1,1,2) plane is observed at a position of 21.78° at a 2θ value. As other main diffraction peaks, a peak corresponding to the (2,0,2) plane is found at a position of 25.54°, a peak corresponding to the (2,1,3) plane is found at a position of 33.58°, and a peak corresponding to the (3,1,2) plane is found at a position of 34.62°, and the intensities of these three peaks are roughly the same. These peaks originate from the crystal components.
[0549] In contrast, Fig.12 The X-ray diffraction pattern of the specific solid electrolyte of Example 2 is shown in FIG. Fig.12 As shown in FIG. 2 , the specific solid electrolyte used in Example 2 satisfies the above-mentioned requirement 3. Fig.11It can be observed that the existing crystalline components are amorphized by the mechanical grinding process, and the sharp peak derived from the lithium tetraborate crystal disappears and becomes broad.
[0550] As a result of X-ray diffraction measurement of each of the specific solid electrolytes prepared in Examples 1, 3, and 4 by the above-mentioned method, it was confirmed that the above-mentioned requirement 3 was satisfied.
[0551] [Example 5]
[0552] <Preparation of Second Lithium Compound>
[0553] As the second lithium compound, LiLaZr oxide (hereinafter also referred to as "LLZO") having a garnet structure containing Li-La-Zr-O, Li2CO3 (99.9%, manufactured by RARE METALLIC Co., Ltd.), La2O3 (96.68%, manufactured by FUJIFILM Wako Pure Chemical Corporation), and ZrO2 (99.9%, manufactured by SHUZUI SCALES CO., LTD.) were used as raw materials and synthesized by a solid phase method. Specifically, the raw material powders were mixed in a mortar and placed on an alumina plate, covered with an alumina crucible, and calcined at 850°C for 12 hours in the atmosphere to synthesize a calcined powder. Pressed powder particles were prepared using the synthesized calcined powder. The obtained pressed powder particles were wrapped with the calcined powder, and formally calcined at 1100-1230°C for 6 hours in the atmosphere to obtain the second lithium compound.
[0554] The lithium ion conductivity of the obtained second lithium compound at 25°C was 3.7×10 -4 S / cm. In addition, regarding the above-mentioned lithium ion conductivity, Au electrodes were set on the surface and back of the particles of the second lithium compound obtained by vapor deposition, and the lithium ion conductivity was estimated by analyzing the arc diameter of the Cole-Cole diagram (Nyquist diagram) obtained in the AC impedance measurement (measurement temperature 25°C, applied voltage 100mV, measurement frequency range 1Hz~1MHz) through two Au electrodes. In addition, the composition of the obtained second lithium compound was analyzed by neutron diffraction method and Rietveld method, and it was confirmed that Li 5.95 Al 0.35 La3Zr2O 12 .
[0555] Furthermore, the particle size distribution of the obtained second lithium compound is about several μm to 10 μm, and the median particle size (D50) is 3.1 μm. In addition, the particle size distribution of the second lithium compound is obtained by the above-mentioned image analysis method, and it is used as the input value for fitting when obtaining the bulk elastic modulus described later. Furthermore, the bulk elastic modulus of the obtained second lithium compound is 105 GPa. The above-mentioned bulk elastic modulus is calculated by the following method. First, the second lithium compound is suspended (concentration: 1.2 mass %) in pure water, the ultrasonic attenuation spectrum is measured, and the bulk elastic modulus of the particles is obtained by fitting based on the scattering attenuation theory formula. The density of the second lithium compound is set to 4.97 g / ml, the Poisson's ratio is set to 0.257, and fitting is performed. An ultrasonic attenuation spectrum that increases monotonically at 10 to 70 MHz is obtained from the second lithium compound. The actual measured ultrasonic attenuation spectrum can be well fitted by the particle size distribution (approximated by the Scjultz distribution with an average of 4.7 μm), the particle density and the scattering attenuation theory with Poisson's ratio as input values.
[0556] <Production and Evaluation of Molded Articles Containing Specific Binder>
[0557] In the same manner as in <Preparation of Specific Solid Electrolyte> in Example 1, a powdery specific binder (complex oxide 1) was prepared.
[0558] The second lithium compound and the specific binder obtained in the above were mixed at a mixing mass ratio of 8:1 (mass of the second lithium compound:mass of the specific binder), and powder compacting was performed at 25°C (room temperature) and an effective pressure of 100 MPa to obtain a powder compact 5 (second specific compact). The lithium ion conductivity of the obtained powder compact 5 was 2.0×10 -6 S / cm. The obtained powder compact 5 was observed by a scanning electron microscope (observation accelerating voltage: 3 kV, EDX: 30 kV), and it was found that the second lithium compound / specific binder interface had good adhesion.
[0559] [Comparative Example 2]
[0560] A powder compact C2 (second specific compact) was obtained by the same procedure as in Example 5 except that LBO powder was used instead of the specific binder and the mixing mass ratio was set to 4:1. The lithium ion conductivity of the obtained powder compact C2 was 1.0×10 -8 The obtained powder compact C2 was observed by scanning electron microscopy (observation acceleration voltage: 3 kV, EDX: 30 kV), and it was clearly found that there were voids at the interface of the second lithium compound / comparative example LBO powder and the adhesion of the second lithium compound / binder interface was poor.
[0561] Table 3 shows the evaluation results of Example 5 and Comparative Example 2.
[0562] In Table 3, the evaluation results of the compressed powder 5 of Example 5 or the compressed powder C2 of Comparative Example 2 are shown in the "Ionic conductivity (S / cm)" column and the "Determination coefficient" column, respectively, and the evaluation results of the composite oxide 5 of Example 5 or the LBO powder of Comparative Example 2 are shown in the "Bulk elastic modulus (GPa)" column, the "Requirement 1-1" column, the "Requirement 1-2" column and the "Half-width ratio of the maximum value (%)" column, respectively.
[0563] In Table 3, the column “Mixing Ratio” shows the mixing ratio of the second lithium compound and the specific binder (or LBO powder) (mass of the second lithium compound:mass of the specific binder (or LBO powder)).
[0564] [Table 3]
[0565]
[0566] As described above, it was confirmed from the comparison between the specific binder of the present invention and the LBO powder of Comparative Example 2 that a molded body having excellent ion conductivity and excellent adhesion can be produced.
[0567] Explanation of symbols
[0568] 1-negative electrode collector, 2-negative electrode active material layer, 3-solid electrolyte layer, 4-positive electrode active material layer, 5-positive electrode collector, 6-working part, 10-all-solid-state secondary battery.
Claims
1. An oxide solid electrolyte, which is represented by the following general formula (I) and satisfies the following requirements 1-1 and 1-2, A a B b O c X d (I) In the general formula (I), A represents at least one selected from Li and Na, X represents at least one selected from F, Cl, Br, I, S, N, H, Se, Te, C, P, Si, Al, Ga, In, Ge, As, Sb and Sn, a represents the number of moles of each element represented by A, which is 1.75<a<2.45, b is 3.75<b<4.25, c is 6.50<c<10.00, d represents the total number of moles of the element represented by X, and is 0<d<0.50, Requirement 1-1: In the reduced two-body distribution function G(r) obtained from the X-ray total scattering measurement of the oxide solid electrolyte, there is a peak located at r of 1.43± The first peak and the top peak in the range of r are located at 2.40± The second peak in the range of , the G(r) of the top of the first peak and the G(r) of the top of the second peak are greater than 1.0, Requirement 1-2: In the reduced two-body distribution function G(r) obtained from the X-ray total scattering measurement of the oxide solid electrolyte, when r is greater than And for In the following range, the absolute value of G(r) is less than 1.
0.
2. The oxide solid electrolyte according to claim 1, wherein The oxide solid electrolyte was solidified at 120°C. 7 The full width at half maximum of the peak whose chemical shift appears in the range of -100 ppm to +100 ppm in the spectrum obtained by Li-NMR measurement is the same as that of the solid phase at 20°C. 7 In the spectrum obtained in the Li-NMR measurement, the ratio of the full width at half maximum of the peak in which the chemical shift appears in the range of -100 ppm to +100 ppm is 70% or less.
3. The oxide solid electrolyte according to claim 1, wherein The oxide solid electrolyte has a Raman spectrum at 600 cm -1 ~850cm -1 The coefficient of determination obtained by linear regression analysis based on the least squares method within the wavenumber region is above 0.9400.
4. The oxide solid electrolyte according to claim 1, wherein The oxide solid electrolyte has a bulk elastic modulus of 45 GPa or less as measured by an ultrasonic attenuation method.
5. The oxide solid electrolyte according to claim 1, wherein The X includes at least one selected from F, Cl, Br, I, Se, Te, and H and at least one selected from C, P, S, and N.
6. An oxide solid electrolyte comprising Li, B, O and X and satisfying the following requirements A-1 and A-2, X represents at least one element selected from F, Cl, Br, I, S, N, H, Se, Te, C, P, Si, Al, Ga, In, Ge, As, Sb and Sn, Requirement A-1: In the reduced two-body distribution function G(r) obtained from the X-ray total scattering measurement of the oxide solid electrolyte, there is a peak located at r of 1.43± The first peak and the top peak in the range of r are located at 2.40± The second peak in the range of , the G(r) of the top of the first peak and the G(r) of the top of the second peak are greater than 1.0, Requirement A-2: In the reduced two-body distribution function G(r) obtained from the X-ray total scattering measurement of the oxide solid electrolyte, when r is greater than And for In the following range, the absolute value of G(r) is less than 1.
0.
7. The oxide solid electrolyte according to claim 6, wherein The oxide solid electrolyte was solidified at 120°C. 7 The full width at half maximum of the peak whose chemical shift appears in the range of -100 ppm to +100 ppm in the spectrum obtained by Li-NMR measurement is the same as that of the solid phase at 20°C. 7 In the spectrum obtained in the Li-NMR measurement, the ratio of the full width at half maximum of the peak in which the chemical shift appears in the range of -100 ppm to +100 ppm is 70% or less.
8. The oxide solid electrolyte according to claim 6, wherein The oxide solid electrolyte has a Raman spectrum at 600 cm -1 ~850cm -1 The coefficient of determination obtained by linear regression analysis based on the least squares method within the wavenumber region is above 0.9400.
9. The oxide solid electrolyte according to claim 6, wherein: The oxide solid electrolyte has a bulk elastic modulus of 45 GPa or less as measured by an ultrasonic attenuation method.
10. The oxide solid electrolyte according to claim 6, wherein: The X includes at least one selected from F, Cl, Br, I, Se, Te, and H and at least one selected from C, P, S, and N.
11. An adhesive, which is represented by the following general formula (I) and satisfies the following requirements 1-1 and 1-2, A a B b O c X d (I) In the general formula (I), A represents at least one selected from Li and Na, X represents at least one selected from F, Cl, Br, I, S, N, H, Se, Te, C, P, Si, Al, Ga, In, Ge, As, Sb and Sn, a represents the number of moles of each element represented by A, which is 1.75<a<2.45, b is 3.75<b<4.25, c is 6.50<c<10.00, d represents the total number of moles of the element represented by X, and is 0<d<0.50, Requirement 1-1: In the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement of the binder, there is a peak located at r of 1.43± The first peak and the top peak in the range of r are located at 2.40± The second peak in the range of , the G (r) of the peak of the first peak and the G (r) of the peak of the second peak are greater than 1.0, and when r is greater than And for In the following range, the absolute value of G(r) is less than 1.0, Requirement 1-2: In the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement of the binder, when r is greater than And for In the following range, the absolute value of G(r) is less than 1.
0.
12. The adhesive according to claim 11, wherein The adhesive was solidified at 120°C. 7 The full width at half maximum of the peak whose chemical shift appears in the range of -100 ppm to +100 ppm in the spectrum obtained by Li-NMR measurement is the same as that of the solid phase at 20°C. 7 In the spectrum obtained in the Li-NMR measurement, the ratio of the full width at half maximum of the peak in which the chemical shift appears in the range of -100 ppm to +100 ppm is 70% or less.
13. The adhesive according to claim 11, wherein The adhesive has a Raman spectrum at 600 cm -1 ~850cm -1 The coefficient of determination obtained by linear regression analysis based on the least squares method within the wavenumber region is above 0.9400.
14. The adhesive according to claim 11, wherein The adhesive has a bulk elastic modulus of 45 GPa or less as measured by an ultrasonic attenuation method.
15. The adhesive according to claim 11, wherein The X includes at least one selected from F, Cl, Br, I, Se, Te, and H and at least one selected from C, P, S, and N.
16. A binder comprising Li, B, O and X and satisfying the following requirements A-1 and A-2: X represents at least one element selected from F, Cl, Br, I, S, N, H, Se, Te, C, P, Si, Al, Ga, In, Ge, As, Sb and Sn, Requirement A-1: In the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement of the binder, there is a peak located at r of 1.43± The first peak and the top peak in the range of r are located at 2.40± The second peak in the range of , the G(r) of the top of the first peak and the G(r) of the top of the second peak are greater than 1.0, Requirement A-2: In the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement of the binder, when r is greater than And for In the following range, the absolute value of G(r) is less than 1.
0.
17. The adhesive according to claim 16, wherein The adhesive was solidified at 120°C. 7 The full width at half maximum of the peak whose chemical shift appears in the range of -100 ppm to +100 ppm in the spectrum obtained by Li-NMR measurement is the same as that of the solid phase at 20°C. 7 In the spectrum obtained in the Li-NMR measurement, the ratio of the full width at half maximum of the peak in which the chemical shift appears in the range of -100 ppm to +100 ppm is 70% or less.
18. The adhesive according to claim 16, wherein The adhesive has a Raman spectrum at 600 cm -1 ~850cm -1 The coefficient of determination obtained by linear regression analysis based on the least squares method within the wavenumber region is above 0.9400.
19. The adhesive according to claim 16, wherein The adhesive has a bulk elastic modulus of 45 GPa or less as measured by an ultrasonic attenuation method.
20. The adhesive according to claim 16, wherein The X includes at least one selected from F, Cl, Br, I, Se, Te, and H and at least one selected from C, P, S, and N. 21 . A solid electrolyte layer located between a positive electrode and a negative electrode, comprising the oxide solid electrolyte according to claim 1 .
22. An active material for an all-solid-state secondary battery, wherein: At least a part of the surface of the active material is coated with a coating layer comprising the oxide solid electrolyte according to any one of claims 1 to 10.
23. An electrode for an all-solid-state secondary battery, comprising: An active material layer comprising an active material and at least one selected from the group consisting of an oxide solid electrolyte according to any one of claims 1 to 10 and a binder according to any one of claims 11 to 20; and Current collector. 24 . An electrode for an all-solid-state secondary battery, comprising an active material layer containing the active material for an all-solid-state secondary battery according to claim 22 and a current collector.
25. An all-solid-state secondary battery comprising a positive electrode, a negative electrode, and a solid electrolyte layer located between the positive electrode and the negative electrode, At least one of the positive electrode, the negative electrode, and the solid electrolyte layer includes at least one selected from the oxide solid electrolyte according to any one of claims 1 to 10 and the binder according to any one of claims 11 to 20.
26. The all-solid-state secondary battery according to claim 25, wherein: The solid electrolyte layer is the solid electrolyte layer according to claim 21.
27. The all-solid-state secondary battery according to claim 25 or 26, wherein: At least one of the positive electrode and the negative electrode is the electrode for an all-solid-state secondary battery according to claim 23 or 24.
Citation Information
Patent Citations
Latex agglutination reaction measuring instrument
JP1987022066A
Catalyst carrier and production thereof
JP1990006856A
Four-wheel steering device
JP1991045473A
Distortion compensator
JP1993090844A
Assignment decision support system
JP1994004516A